FeSi-Ni3Si / TiB2-TiC composite material and molten metal liquid phase sintering process thereof

Through the molten metal liquid phase sintering process of FeSi-Ni3Si/TiB2-TiC composite material, the problems of high cost and complex process of existing composite materials are solved, and low-cost and high-performance composite material preparation is achieved, which is suitable for industrial production.

CN119794332APending Publication Date: 2025-04-11XI'AN PETROLEUM UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411964744.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

The existing composite materials have high cost and complex processes, making it difficult to prepare products with complex shapes, which limits their wide application in the engineering field.

Method used

FeSi-Ni3Si/TiB2-TiC composite material and its molten metal liquid phase sintering process are used to prepare FeSi and Ni3Si intermetallic compound powders through mechanical alloying process and heat treatment process, combined with Al2O3 and Y2O3 as sintering aids, and phenolic resin as binder, pressure forming and molten metal liquid phase sintering are performed.

Benefits of technology

The characteristics of simple operation process, low production cost, and unlimited product shape and size are achieved, and FeSi-Ni3Si/TiB2-TiC composite blocks with high density and excellent mechanical properties are prepared.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119794332A_ABST
    Figure CN119794332A_ABST
Patent Text Reader

Abstract

The FeSi-Ni3Si / TiB2-TiC composite material comprises the following components in parts by mass: a FeSi intermetallic compound and a Ni3Si intermetallic compound are used as reinforcing and toughening phases; tiB2 and TiC are used as matrixes; al2O3 powder; y2O3 powder; a phenolic resin binder; the molten metal liquid phase sintering process preparation method comprises the following steps: step 1, preparing Fe-Si intermetallic compound powder A; secondly, the Fe-Si intermetallic compound powder A is subjected to heat treatment, and then FeSi intermetallic compound powder is obtained; thirdly, Ni-Si intermetallic compound powder B is prepared; fourthly, the Ni-Si intermetallic compound powder B is subjected to a heat treatment process, and Ni3Si intermetallic compound powder is obtained; step 5, preparing FeSi-Ni3Si / TiB2-TiC composite powder, and preparing FeSi-Ni3Si / TiB2-TiC Step 6, preparing a FeSi-Ni3Si / TiB2-TiC composite powder strip-shaped test sample prefabricated blank body; 7, the FeSi-Ni3Si / TiB2-TiC composite powder strip-shaped sample prefabricated blank is put into a vacuum high-temperature sintering furnace to be subjected to a molten metal liquid phase sintering process; the FeSi-Ni3Si / TiB2-TiC composite material has the advantages that the preparation efficiency is high, the process is simple, and the FeSi-Ni3Si / TiB2-TiC composite material has high density and high mechanical properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of composite materials and preparation thereof, and in particular relates to a FeSi-Ni3Si / TiB2-TiC composite material and a molten metal liquid phase sintering process thereof. Background Art

[0002] The density of FeSi (iron silicon alloy) is 6.37g / cm 3 , the melting point is 1410℃, FeSi is insoluble in water and acid, but it is paramagnetic at high temperature and antiferromagnetic at low temperature. In addition, the electronic structure study of FeSi shows that it exhibits metallic properties. FeSi alloy (iron silicon alloy) has a variety of excellent properties, including good electromagnetic properties, corrosion resistance and temperature stability. FeSi alloy is mainly used in electronic devices such as high current power inductors, circuit inductors, smooth yoke coils and converters. It is favored for its excellent DC superposition characteristics, high saturation magnetic induction and good storage capacity. FeSi alloy has high saturation magnetic induction and high magnetic permeability, which makes it perform well in electromagnetic devices. In addition, the addition of an appropriate amount of Cr element can optimize the microstructure of FeSi alloy, further improve its magnetic permeability and reduce reflection loss. FeSi alloy has good temperature stability and can maintain its performance stability under different temperature environments. This makes it widely used in electronic devices that require temperature control.

[0003] Ni3Si intermetallic compound has excellent resistance to sulfur dioxide corrosion and good high-temperature oxidation resistance. It is a potential high-temperature structural material and is expected to be used in petrochemical, metallurgical, aerospace and other places that require high temperature and corrosion resistance. It can also replace some high-temperature structural materials with poor specific strength. However, Ni3Si materials have low ductility, low fracture toughness, and poor high-temperature creep resistance. These shortcomings greatly limit its application as a structural material in practice. In order to improve the performance of Ni3Si, researchers have adopted different methods, such as using advanced laser technology, Bridgman directional solidification technology, electron beam zone melting technology, etc., to study Ni3Si intermetallic compounds through alloying and composite methods, in order to improve its comprehensive mechanical properties and high-temperature strength. Specifically, the comprehensive mechanical properties of the material can be improved by combining Ni3Si intermetallic compounds with ductile metal Ni during liquid-solid phase transition through eutectic reaction. In addition, Ni3Si powder alloy, bulk alloy and Ni / Ni3Si composite materials were prepared by high-energy ball milling, hot pressing sintering and vacuum melting, and their microstructure and properties were further analyzed and optimized. These studies not only reveal the relationship between the microstructure and properties of Ni3Si-based materials, but also provide a theoretical and practical basis for the application and development of Ni3Si-based high-temperature ordered alloys. Although Ni3Si has excellent high-temperature oxidation resistance and corrosion resistance, its inherent brittleness and low high-temperature strength are still the main factors limiting its wide application. Therefore, improving its comprehensive performance through material composite and process optimization has become an important research direction. Ni3Si is a new type of structural material with high temperature resistance, high strength and corrosion resistance. Ni3Si has high strength, low density, excellent high-temperature oxidation resistance and corrosion resistance. Ni3Si has high hardness, and its hardness can reach more than HV1000. In addition, Ni3Si has a high melting point of about 1255℃ and good thermal stability. Ni3Si exhibits good oxidation resistance and corrosion resistance at high temperatures. Ni3Si has good thermoelectric stability above 1000℃. Due to the high temperature strength and oxidation resistance of Ni3Si, it is widely used in the field of high temperature alloys and corrosion resistant materials. Ni3Si intermetallic compounds have excellent resistance to sulfur dioxide corrosion and good high temperature oxidation resistance. They are potential high temperature structural materials and are expected to be used in situations requiring high temperature resistance and corrosion resistance. They can also replace some of the currently used high temperature structural materials with poor specific strength. Nickel silicon intermetallic compounds have high mechanical properties, good wear resistance, corrosion resistance, and high temperature oxidation resistance, and have been widely used in the industrial field. Nickel silicon intermetallic compounds mainly include Ni3Si intermetallic compounds. Since Ni3Si intermetallic compounds have many excellent properties, they are widely used in the engineering field.Ni3Si intermetallic compounds are widely used in the engineering field due to their high strength, high toughness, high hardness, good wear resistance and high temperature oxidation resistance.

[0004] TiB2 (titanium diboride) has a series of excellent physical and chemical properties, which makes it widely used in many fields. TiB2 has extremely high hardness, even harder than diamond, and has excellent wear resistance, which can resist high-speed friction and wear. These characteristics make TiB2 have important application value in the manufacture of high-strength, wear-resistant tools, cutters and abrasives. TiB2 has good thermal conductivity and can be used in thermal management and cooling applications. At the same time, it has a high melting point and thermal stability, which enable it to maintain good performance under high temperature and harsh environment. TiB2 has excellent electrical conductivity and high thermal conductivity and electrical conductivity, which makes it of great value in the application field of electronic devices. Due to the excellent performance of TiB2, it is widely used in many fields such as metal ceramics, functional gradient cemented carbide, ceramic cutting tools, electronic packaging materials, microelectronic devices, etc. For example, as a ceramic cutting tool material, TiB2 greatly improves cutting efficiency and is considered to be one of the best tools for improving machining productivity. TiB2 plays an indispensable role in many industrial fields due to its high hardness, excellent wear resistance, good thermal and electrical conductivity, high melting point and chemical stability. Titanium diboride (TiB2) is an important ceramic material with excellent physical and chemical properties, and is widely used in metal ceramics and functionally gradient cemented carbides. First of all, titanium diboride has extremely high hardness and thermal stability, good wear resistance and corrosion resistance, and can maintain good performance under high temperature and harsh environment. This makes it an ideal choice for metal ceramics for manufacturing high-strength, wear-resistant tools, knives and abrasives. Secondly, titanium diboride has excellent electrical conductivity and has high thermal and electrical conductivity. In addition, titanium diboride can also be used in the preparation of functionally gradient cemented carbides. Functionally gradient cemented carbide is a material whose composition, structure and properties vary in space in a gradient. By controlling the content and distribution of titanium diboride, the purpose of forming a gradient structure in cemented carbide can be achieved. This structure enables the material to have optimized properties in different regions, such as hardness, toughness and corrosion resistance, to meet different application requirements. As an important ceramic material, titanium diboride is widely used in metal ceramics and functional gradient cemented carbides. Its excellent hardness, thermal stability and electrical conductivity provide innovative solutions for various industrial fields. Titanium diboride (TiB2) is a new type of ceramic material that has dual uses as structural ceramics and functional ceramics. It has extremely excellent physical and chemical properties, extremely high melting point, extremely high hardness, excellent chemical stability, high oxidation resistance temperature, and excellent mechanical properties at high temperatures. Titanium diboride has high hardness, wear resistance and high temperature resistance. TiB2 is widely used in the industrial field due to its hardness and wear resistance, especially as a coating material to enhance the wear resistance of metal surfaces.It is also used to make ceramic tools and cutters that are able to maintain their stability and hardness under high temperatures and pressures, making it ideal for grinding, cutting and machining hard materials.

[0005] TiC (titanium carbide) has many excellent properties, including high hardness, high melting point, good electrical and thermal conductivity, high wear resistance and chemical stability. These properties make TiC widely used in many fields. The hardness of TiC is generally between 26-31GPa. The melting point of TiC is very high, which allows it to maintain stable performance in high temperature environments. The electrical conductivity of TiC decreases with increasing temperature, showing metallic properties. Its thermal conductivity also makes it have application potential in thermal management. TiC has excellent wear resistance and corrosion resistance, and can maintain stable performance for a long time in harsh environments. Due to these excellent properties, TiC is widely used in the following fields. In the field of wear-resistant materials, TiC, as a wear-resistant material, can greatly reduce the wear rate and improve precision and finish. In the field of cutting tool materials, due to its high hardness and wear resistance, TiC is often used to manufacture cutting tools to improve the service life and cutting efficiency of the tools. In the field of the electronics industry, the high electrical conductivity of TiC makes it of great value in the electronics industry and can be used to manufacture high-performance electronic components. In the aerospace field, TiC's high temperature stability and strength make it widely used in the aerospace field and can withstand extreme conditions. Titanium carbide (TiC) is a compound of carbon and titanium with high temperature resistance, high strength, high hardness, high wear resistance, corrosion resistance and other properties. It is widely used in the manufacture of wear-resistant materials, cutting tool materials, aerospace and many other fields. At present, titanium carbide has become a wear-resistant material with great application value in the market. The wear resistance of titanium carbide is comparable to that of artificial diamond, and its hardness can generally reach HRA90 or above. At the same time, it can withstand high temperatures of 300°C and has been widely used. The production of wear-resistant products using titanium carbide materials can greatly reduce costs and wear rates.

[0006] Titanium diboride ceramic materials are widely used in the engineering field because of their high strength and hardness, good wear resistance and high temperature oxidation resistance. Titanium diboride materials belong to cemented carbide. However, titanium diboride ceramics are brittle and have low fracture toughness, so it is necessary to add a reinforcing and toughening phase to the TiB2 matrix. Titanium carbide ceramic materials are widely used in the engineering field because of their high strength and hardness, good wear resistance and high temperature oxidation resistance. Titanium carbide materials belong to cemented carbide. However, titanium carbide ceramics are brittle and have low fracture toughness, so it is necessary to add a reinforcing and toughening phase to the TiC matrix. FeSi intermetallic compounds can be used as reinforcing and toughening phases for titanium diboride ceramics and titanium carbide ceramics because of their high flexural strength and fracture toughness. Ni3Si intermetallic compounds can be used as reinforcing and toughening phases for titanium diboride ceramics and titanium carbide ceramics because of their high flexural strength and fracture toughness. Therefore, FeSi intermetallic compounds and Ni3Si intermetallic compounds can be added to titanium diboride ceramics and titanium carbide ceramics to form FeSi-Ni3Si / TiB2-TiC composite materials, which can greatly improve the flexural strength and fracture toughness of titanium diboride ceramics and titanium carbide ceramics. FeSi intermetallic compounds and Ni3Si intermetallic compounds have good compatibility with TiB2 ceramics and TiC ceramics. FeSi intermetallic compounds and Ni3Si intermetallic compounds can be added to TiB2 matrix and TiC matrix to form FeSi-Ni3Si / TiB2-TiC composite materials through compounding, which will greatly improve and enhance the mechanical properties of TiB2 ceramics and TiC ceramic materials. Therefore, the preparation of FeSi-Ni3Si / TiB2-TiC composite materials has become a major research focus and hotspot. TiB2 ceramics and TiC ceramic materials are compounded to form TiB2-TiC composite ceramics, which have higher mechanical properties, higher hardness and excellent wear resistance, and have better performance than single-phase TiB2 ceramics and single-phase TiC ceramics. In order to improve the mechanical properties and wear resistance of TiB2-TiC composite ceramics, FeSi intermetallic compounds and Ni3Si intermetallic compounds can be compounded with TiB2-TiC composite ceramics to prepare FeSi-Ni3Si / TiB2-TiC composite materials. FeSi-Ni3Si / TiB2-TiC composite materials have the excellent properties of FeSi intermetallic compounds and Ni3Si intermetallic compounds, as well as the excellent properties of TiB2 ceramics and TiC ceramic materials.

[0007] In the prior art, the pressureless sintering process is used to sinter under the condition of no pressure, and a dense composite material block cannot be obtained at all, and only a composite material block with extremely high porosity can be obtained, so the pressureless sintering process cannot be used for preparation. Although the hot isostatic pressing sintering process can obtain a dense composite material block, the preparation cost of the hot isostatic pressing sintering process is too high, the hot isostatic pressing machine equipment is expensive, and the preparation process is too complicated, so the hot isostatic pressing sintering process cannot be used for preparation. Although the spark plasma sintering process can obtain a dense composite material block, the preparation cost of the spark plasma sintering process is too high, the spark plasma sintering equipment is expensive, and the preparation process is too complicated, so the spark plasma sintering process cannot be used for preparation. Therefore, the powder metallurgy sintering process has a high preparation cost, a relatively complicated preparation process, and is difficult to prepare a composite material product with a complex shape, so it is difficult to carry out industrial production and difficult to achieve industrialization, which limits the wide application of composite materials in the engineering field.

[0008] At present, most researchers use hot pressing and sintering process to prepare composite material blocks. However, due to the high cost of hot pressing and sintering process, the preparation process is relatively complicated, and it is difficult to prepare composite products with complex shapes. Therefore, it is difficult to carry out industrial production and difficult to achieve industrialization, which limits the widespread application of composite materials in the engineering field. Summary of the invention

[0009] In order to overcome the deficiencies of the above-mentioned prior art, the purpose of the present invention is to propose a FeSi-Ni3Si / TiB2-TiC composite material and a molten metal liquid phase sintering process thereof, which has the characteristics of simple operation process, low preparation cost, and no restrictions on the shape and size of the prepared product.

[0010] To achieve the above object, the technical solution adopted by the present invention is:

[0011] The FeSi-Ni3Si / TiB2-TiC composite material includes the following components in parts by mass:

[0012] FeSi intermetallic compound and Ni3Si intermetallic compound are used as strengthening and toughening phases, TiB2 and TiC are used as matrix; Al2O3 and Y2O3 are used as sintering aids; a small amount of phenolic resin is used as binder;

[0013] The mass fraction of FeSi intermetallic compound powder is 5 to 35 parts; the mass fraction of Ni3Si intermetallic compound powder is 5 to 35 parts; the mass fraction of TiB2 powder is 15 to 45 parts; the mass fraction of TiC powder is 15 to 45 parts; the mass fraction of Al2O3 powder is 3 to 9 parts; the mass fraction of Y2O3 powder is 1 to 7 parts; the mass fraction of phenolic resin binder is 9 to 10 parts;

[0014] The mass ratio of the FeSi intermetallic compound powder to the Ni3Si intermetallic compound powder is 1:1.

[0015] The molar ratio of Fe powder to Si powder in the FeSi intermetallic compound powder is 50:50;

[0016] The molar ratio of Ni powder to Si powder in the Ni3Si intermetallic compound powder is 75:25;

[0017] Both FeSi intermetallic compound powder and Ni3Si intermetallic compound powder are prepared by mechanical alloying process and heat treatment process.

[0018] The molten metal liquid phase sintering process of the FeSi-Ni3Si / TiB2-TiC composite material comprises the following steps by weight:

[0019] Step 1: prepare Fe-Si intermetallic compound powder by mechanical alloying process, the specific steps are:

[0020] Fe-Si intermetallic compound powder is prepared by ball milling for 80 hours using a mechanical alloying process, wherein the ball milling jar is a polytetrafluoroethylene ball milling jar, the grinding balls are agate grinding balls, the mass ratio of the agate grinding balls to the mixed powder is 10:1, wherein the molar ratio of Fe powder to Si powder is 50:50, Fe powder and Si powder are loaded into the ball milling jar of a QM-1SP2 planetary ball mill, and after fixing four ball milling jars, the planetary ball mill is started for mechanical ball milling, the mechanical ball milling time is 80 hours, the speed of the ball mill is 400r / min, dry ball milling is adopted, and intermittent ball milling is adopted, argon gas is filled into the ball milling jar as a protective gas, and Fe-Si intermetallic compound powder is prepared by ball milling for 80 hours using a mechanical alloying process; the purity of the Fe powder is 99%, and the particle size is 75-100μm; the purity of the Si powder is 99%, and the particle size is 75-100μm;

[0021] Step 2: The Fe-Si intermetallic compound powder prepared in step 1 is subjected to a heat treatment process to prepare FeSi intermetallic compound powder. The specific steps are:

[0022] The Fe-Si intermetallic compound powder and 10 parts of phenolic resin binder are placed in a ball mill, and 300 ml of anhydrous ethanol and 30 agate grinding balls with a diameter of 15 mm are added. The mixture is mechanically ball-milled for 24 hours to prepare a slurry, which is then mixed by wet ball milling to prepare a slurry. The slurry is placed in a glass beaker, and the glass beaker is placed in an oven and dried at 100°C for 24 hours to prepare a mixed powder A. The mixed powder A is placed in a steel mold for preparing a strip sample, and is pressed into a strip sample by a pressure molding machine at a pressure of 100MPa to 200MPa for a holding time of 3 minutes. The size of the strip sample is 50mm×5mm×6mm, and the strip sample is placed in a graphite crucible, and the graphite crucible is placed in a vacuum sintering furnace, wherein the heat treatment temperature is 800°C to 1200°C, the holding time is 1h, and the vacuum degree is 10 -2 Pa, a FeSi intermetallic compound powder strip sample with a porous structure is obtained through a heat treatment process, after the heat treatment process, the FeSi intermetallic compound strip sample is taken out, crushed and ground into FeSi intermetallic compound powder, and FeSi intermetallic compound powder is prepared through a heat treatment process; a small amount of phenolic resin is completely decomposed and volatilized during the high-temperature heat treatment process, and no phenolic resin remains in the obtained powder;

[0023] Step 3: Prepare Ni-Si intermetallic compound powder by mechanical alloying process. The specific steps are:

[0024] The Ni-Si intermetallic compound powder is prepared by ball milling for 80 hours using a mechanical alloying process, wherein the ball milling jar is a polytetrafluoroethylene ball milling jar, the grinding balls are agate grinding balls, the mass ratio of the agate grinding balls to the mixed powder is 10:1, and the molar ratio of the Ni powder to the Si powder is 75:25; the Ni powder and the Si powder are loaded into the ball milling jar of the QM-1SP2 planetary ball mill, and the planetary ball mill is started after the four ball milling jars are fixed for mechanical ball milling, the mechanical ball milling time is 80 hours, the speed of the ball mill is 400r / min, dry ball milling is adopted, and intermittent ball milling is adopted, argon gas is filled into the ball milling jar as a protective gas, and the Ni-Si intermetallic compound powder is prepared by ball milling for 80 hours using a mechanical alloying process; the purity of the Ni powder is 99%, and the particle size is 75-100μm; the purity of the Si powder is 99%, and the particle size is 75-100μm;

[0025] Step 4: The Ni-Si intermetallic compound powder prepared in step 3 is subjected to a heat treatment process to prepare Ni3Si intermetallic compound powder. The specific steps are:

[0026] The Ni-Si intermetallic compound powder and 10 parts of phenolic resin binder are placed in a ball mill, and 300 ml of anhydrous ethanol and 30 agate grinding balls with a diameter of 15 mm are added and mechanically ball milled for 24 hours to prepare a slurry, which is then mixed by wet ball milling to prepare a slurry, and the slurry is placed in a glass beaker, and the glass beaker is placed in an oven and dried at 100°C for 24 hours to prepare a mixed powder B, and the mixed powder B is placed in a steel mold for preparing a strip sample, and is pressed into a strip sample by a pressure molding machine at a pressure of 100MPa to 200MPa for a holding time of 3 minutes, and the size of the strip sample is 50mm×5mm×6mm, and the strip sample is placed in a graphite crucible, and the graphite crucible is placed in a vacuum sintering furnace, wherein the heat treatment temperature is 800°C to 1200°C, the holding time is 1h, and the vacuum degree is 10 -2 Pa, a porous Ni3Si intermetallic compound powder strip sample is obtained through the heat treatment process, and the Ni3Si intermetallic compound strip sample is taken out after the heat treatment process, and then crushed and ground into Ni3Si intermetallic compound powder; Ni3Si intermetallic compound powder is prepared through the heat treatment process; a small amount of phenolic resin is completely decomposed and volatilized during the high-temperature heat treatment process, and no phenolic resin remains in the obtained powder;

[0027] Step 5: Mix 5 to 35 parts of the FeSi intermetallic compound powder and 5 to 35 parts of the Ni3Si intermetallic compound powder prepared in step 2 and step 4 with 15 to 45 parts of the TiB2 powder and 15 to 45 parts of the TiC powder, add 3 to 9 parts of the Al2O3 powder and 1 to 7 parts of the Y2O3 powder as sintering aids to the mixed powder to obtain a mixed powder C, and put the obtained FeSi intermetallic compound powder and Ni3Si intermetallic compound powder into a ball mill, add 100 to 400 ml of anhydrous ethanol and 30 to 60 balls with a diameter of 10 to 16 mm into the ball mill. agate grinding balls, mechanically ball milling and mixing for 24 hours to make a slurry, the slurry is put into a glass beaker and the glass beaker is placed in an oven and dried at 100°C for 24 hours to prepare a FeSi-Ni3Si / TiB2-TiC composite powder; wherein the mass fractions of FeSi intermetallic compound powder and Ni3Si intermetallic compound powder in the FeSi-Ni3Si / TiB2-TiC composite powder are 10 to 70 parts; wherein the mass ratio of FeSi intermetallic compound powder and Ni3Si intermetallic compound powder in the FeSi-Ni3Si / TiB2-TiC composite powder is 1:1; the mass ratio of TiB2 powder and TiC powder in the FeSi-Ni3Si / TiB2-TiC composite powder is 1:1;

[0028] Step 6: The FeSi-Ni3Si / TiB2-TiC composite powder obtained in step 5 is mixed with 9 to 10 parts of a phenolic resin binder to prepare a mixed powder, which is then loaded into a ball mill and mixed with 300 ml of anhydrous ethanol and 30 agate grinding balls with a diameter of 15 mm for mechanical ball milling for 24 hours to prepare a slurry, which is then mixed by wet ball milling to prepare a slurry and loaded into a glass beaker, and the glass beaker is placed in an oven and dried at 100°C for 24 hours to prepare a mixed powder D containing a phenolic resin binder, and the mixed powder D containing a small amount of phenolic resin binder is loaded into a steel mold for preparing a strip sample, and is pressed into a strip sample preform by a pressure molding machine at a pressure of 100 MPa to 200 MPa for a holding time of 3 minutes, and the size of the strip sample preform is 50 mm×5 mm×6 mm; The sample preform is placed in a drying oven and dried at 150° C. for 24 hours to completely solidify the phenolic resin, thereby obtaining a FeSi-Ni3Si / TiB2-TiC composite powder strip sample preform containing a phenolic resin binder having a certain strength. The FeSi-Ni3Si / TiB2-TiC composite powder strip sample preform is placed in a latex glove, wrapped and sealed with a latex glove, and placed in a cold isostatic press. The medium in the cold isostatic press is hydraulic oil. The holding time in the cold isostatic press is 5 minutes at a pressure of 100 MPa to 200 MPa. After the holding time, the sample is taken out and isostatically pressed by the cold isostatic press to form a dense FeSi-Ni3Si / TiB2-TiC composite powder strip sample preform. The size of the strip sample preform is 50 mm×5 mm×6 mm.

[0029] Step 7: Place the FeSi-Ni3Si / TiB2-TiC composite powder strip sample preformed body prepared by pressure forming in step 6 into a graphite crucible, and place the graphite crucible into a vacuum high-temperature sintering furnace for a molten metal liquid phase sintering process; the molten metal liquid phase sintering process is as follows: the sintering temperature is 1500°C to 1800°C, the holding time is 2h, and the molten metal liquid phase sintering process is carried out under vacuum conditions, and the vacuum degree is 10 -2Pa, the heating rate during the sintering process is 10-35℃ / min, and the furnace is cooled after the sintering process is completed; the melting point of the FeSi intermetallic compound is 1410℃, and the melting point of the Ni3Si intermetallic compound is 1255℃. When sintering at 1500℃-1800℃, the FeSi intermetallic compound and the Ni3Si intermetallic compound will melt to form a liquid phase, and the FeSi intermetallic compound liquid phase and the Ni3Si intermetallic compound liquid phase will penetrate through the pores in the TiB2 matrix and the TiC matrix into the middle of the TiB2 particles and the TiC particles, so that the molten FeSi intermetallic compound liquid phase and the molten Ni3Si intermetallic compound liquid phase fill the TiB2 ceramic The pores in the TiC ceramic matrix are formed by the good wettability of the FeSi alloy liquid phase particles and the Ni3Si alloy liquid phase particles with the TiB2 particles and the TiC particles. The FeSi intermetallic compound and the Ni3Si intermetallic compound can be well bonded with the TiB2 particles and the TiC particles to form a dense FeSi-Ni3Si / TiB2-TiC composite sintered block; and the higher the content of the FeSi alloy and the Ni3Si alloy, the denser the FeSi-Ni3Si / TiB2-TiC composite material is. During the sintering process, the Al2O3 powder and the Y2O3 powder sintering aid react at high temperature to form a liquid Y3Al5O 12 , namely YAG phase, forming a liquid phase to promote the densification of the ceramic composite matrix and improve the mechanical properties of the ceramic composite. The phenolic resin binder decomposes into gas and volatilizes at high temperature, leaving only a small amount of residual carbon, which is mixed in the sintered sample; so the molten metal liquid phase sintering process preparation method can prepare FeSi-Ni3Si / TiB2-TiC composite block with high density and high mechanical properties, so the molten metal liquid phase sintering process preparation method can prepare FeSi-Ni3Si / TiB2-TiC composite block; wherein the mass fraction of FeSi intermetallic compound powder and Ni3Si intermetallic compound powder in FeSi-Ni3Si / TiB2-TiC composite material is 10 to 70 parts.

[0030] The average particle size of the FeSi intermetallic compound powder and the Ni3Si intermetallic compound powder is 10-15 μm, and the powder particle size is extremely fine; the FeSi intermetallic compound powder and the Ni3Si intermetallic compound powder have an ordered structure.

[0031] The step five: wherein the particle size of the TiB2 powder is 5 to 8 μm and the particle size of the TiC powder is 5 to 8 μm; the mass fractions of the FeSi intermetallic compound powder and the Ni3Si intermetallic compound powder in the FeSi-Ni3Si / TiB2-TiC composite powder are 10 to 70 parts; the mass ratio of the FeSi intermetallic compound powder and the Ni3Si intermetallic compound powder is 1:1; the mass ratio of the TiB2 ceramic powder and the TiC ceramic powder is 1:1.

[0032] The beneficial effects of the present invention are:

[0033] The present invention proposes to prepare FeSi-Ni3Si / TiB2-TiC composite material blocks by using a molten metal liquid phase sintering process. The traditional hot pressing sintering process has high cost and complex preparation process. The shape and size of the prepared products are limited, making it difficult to achieve large-scale production and industrialization. However, by using a molten metal liquid phase sintering process, only the pressure-formed blank needs to be sintered. The molten metal liquid phase sintering process has low preparation cost and simple preparation process. It can produce sintered products with complex shapes, is easy to industrialize, and is conducive to industrialization. At the same time, since the sintering process of the FeSi-Ni3Si / TiB2-TiC composite material is under the condition of being higher than the melting point of the FeSi intermetallic compound and the melting point of the Ni3Si intermetallic compound, wherein the melting point of the FeSi intermetallic compound is 1410°C, the melting point of the Ni3Si intermetallic compound is 1255°C, and the sintering temperature is 1500°C-1800°C, at this temperature, the FeSi intermetallic compound has melted to form a liquid phase, and the Ni3Si intermetallic compound has melted to form a liquid phase, and the formed FeSi intermetallic compound liquid phase and Ni3Si intermetallic compound liquid phase are filled into the pores in the TiB2 matrix and the TiC matrix, and the FeSi alloy liquid phase and the Ni3Si alloy liquid phase are bonded together with the TiB2 particles and the TiC particles through the molten metal liquid phase sintering process to form a dense sintered block. The FeSi-Ni3Si / TiB2-TiC composite material is prepared by the molten metal liquid phase sintering process. The molten metal liquid phase sintering process can produce sintered products with high density and uniform and dense microstructure, and the sintered products also have high mechanical properties. The purpose of adding 10 parts by mass of Al2O3 powder and Y2O3 powder sintering aids is that during the sintering process, the Al2O3 powder and Y2O3 powder sintering aids react at high temperature to form liquid Y3Al5O 12, i.e. YAG phase, forms a liquid phase to promote the densification of the ceramic composite matrix, plays a role in filling pores, and improves the mechanical properties of the ceramic composite. Adding 10 parts of phenolic resin binder by mass to the FeSi-Ni3Si / TiB2-TiC composite powder is to improve the strip sample blank after pressure forming to have a certain strength and hardness, prevent fracture and damage when taking samples and putting them into graphite crucibles, and ensure the integrity of the strip sample blank. The phenolic resin binder decomposes into gas at high temperature during the sintering process and volatilizes away, leaving only a small amount of residual carbon, which is mixed in the sample after sintering and will not affect the final product. Therefore, the FeSi-Ni3Si / TiB2-TiC composite block prepared by the molten metal liquid phase sintering process preparation method of the present invention has the advantages of low cost and high performance, and can also prepare parts with complex shapes according to engineering needs, so the present invention has important significance and practical value.

[0034] The present invention proposes to prepare FeSi-Ni3Si / TiB2-TiC composite material blocks by using a molten metal liquid phase sintering process. The molten metal liquid phase sintering process, the process of which is: firstly, the FeSi-Ni3Si / TiB2-TiC composite powder is formed into a desired shape by pressure molding, and then the molten metal liquid phase sintering process is carried out in a high-temperature sintering furnace to prepare FeSi-Ni3Si / TiB2-TiC composite material products. The molten metal liquid phase sintering process has a low preparation cost and a simple preparation process, and can be used to prepare FeSi-Ni3Si / TiB2-TiC composite material products with complex shapes, which is suitable for industrial production and is conducive to industrialization. Therefore, the present invention proposes to prepare FeSi-Ni3Si / TiB2-TiC composite material blocks by using a molten metal liquid phase sintering process. Firstly, FeSi intermetallic compound powder and Ni3Si intermetallic compound powder were prepared by mechanical alloying process and heat treatment process, and the FeSi intermetallic compound powder and Ni3Si intermetallic compound powder were mixed with TiB2 powder and TiC powder to prepare FeSi-Ni3Si / TiB2-TiC composite powder, and 10 parts by mass of Al2O3 powder and Y2O3 powder sintering aids were added to prepare FeSi-Ni3Si / TiB2-TiC composite powder by wet ball milling and drying, and strip sample preforms were prepared by pressure forming, and FeSi-Ni3Si / TiB2-TiC composite material blocks were prepared by molten metal liquid phase sintering process. The molten metal liquid phase sintering method adopted in the present invention is to utilize the condition that the sintering temperature is 1500℃~1800℃ which is higher than the melting point of FeSi intermetallic compound and the melting point of Ni3Si intermetallic compound, wherein the melting point of FeSi intermetallic compound is 1410℃, and the melting point of Ni3Si intermetallic compound is 1255℃, the FeSi intermetallic compound will melt to form a liquid phase, the Ni3Si intermetallic compound will melt to form a liquid phase, the FeSi intermetallic compound liquid phase particles and the Ni3Si intermetallic compound liquid phase particles can be sintered with TiB2 particles and TiC particles into a dense FeSi-Ni3Si / TiB2-TiC composite material block, so the FeSi-Ni3Si / TiB2-TiC composite material block is prepared by the molten metal liquid phase sintering process method.

[0035] Liquid phase sintering process is the main method for preparing metal matrix composites, metal ceramic composites, and intermetallic compound / ceramic matrix composites. The properties of liquid phase sintering process include sintering with the coexistence of liquid phase and solid phase particles. The characteristics of liquid phase sintering process are fast speed, significant shrinkage, densification, etc. Liquid phase sintering is a new method of material sintering process. Liquid phase sintering has the characteristics of fast heating speed, high energy utilization rate, high heating efficiency, etc., and can improve the uniformity and yield of products, improve the microstructure and performance of sintered materials, and has become a new research hotspot in the field of material sintering. Therefore, sintered products with higher density are obtained through liquid phase sintering process. Composite materials can be prepared by liquid phase sintering process. Liquid phase sintering refers to a sintering method in which at least one component can form a liquid phase at the sintering temperature, and the powder particles are rearranged and densified through the flow, dissolution-precipitation and other processes of the liquid phase. This process can achieve higher density at a lower temperature and is very effective for the preparation of some refractory metals or cemented carbides. The principle of liquid phase sintering includes the process of particle rearrangement. In the early stage of sintering, when the liquid phase appears, the solid particles slide and rotate under the capillary force of the liquid phase, thereby achieving the rearrangement of the particles. This rearrangement can make the particles stack more tightly and quickly reduce the volume of pores. For example, in the liquid phase sintering process of metal ceramic materials, the metal phase forms a liquid phase at the sintering temperature, and the ceramic particles will adjust their positions under the action of liquid metal. In the dissolution-precipitation process, the liquid phase can dissolve some solid particles, and these dissolved substances will diffuse in the liquid phase and then re-precipitate on the surface of other particles. This process helps to eliminate the pores between particles and can make the particles more closely bonded. Taking tungsten-copper (W-Cu) alloy as an example, during liquid phase sintering, the tungsten atoms on the surface of tungsten particles will dissolve in the copper liquid phase and then precipitate on the surface of other tungsten particles, thereby making the bond between tungsten particles stronger and improving the density of the alloy. In addition to the above-mentioned liquid phase-dominated process, the solid-state sintering process will also occur in the later stage of sintering when the amount of liquid phase decreases or the liquid phase solidifies. At this time, the density and strength of the material are further improved mainly through diffusion between particles. In the process of liquid phase sintering, the raw material preparation process must first select the appropriate raw material powder. Factors such as the particle size, shape and purity of the powder have a great influence on the effect of liquid phase sintering. Generally speaking, the smaller the powder particle size, the more conducive it is to the particle rearrangement and dissolution-precipitation process during the sintering process. For example, when preparing cemented carbide, tungsten carbide (WC) powder and metal binder (such as cobalt Co) powder with a particle size of micron or even submicron are usually selected. Then mix them in a certain proportion, and the uniformity of the mixing is also critical. Mechanical mixing methods, such as ball milling mixing, can be used to evenly mix different powders through the collision and grinding of the grinding balls in the ball mill. In the pressing molding process, the mixed powder is placed in a mold and formed into the desired shape by pressure.Parameters such as the size of the pressing pressure and the holding time will affect the density and strength of the green body. If the pressure is insufficient, the density of the green body is low, and large shrinkage deformation may occur during the sintering process; if the pressure is too high, the mold may be damaged or defects such as delamination may occur in the green body. Generally, cold isostatic pressing or molding methods are used. Sintering process, sintering is a key step in the liquid phase sintering process. The green body is placed in a high-temperature furnace and heated to the temperature at which the liquid phase is formed. The determination of this temperature needs to be determined according to the material system, which is usually higher than the melting point of the liquid phase component. During the sintering process, parameters such as the heating rate, sintering temperature and holding time must be strictly controlled. Too fast a heating rate may cause thermal stress inside the green body, resulting in cracks; too high a sintering temperature or too long a holding time may cause too much liquid phase, resulting in deformation of the shape of the material or coarse tissue. If the sintering temperature is too low or the holding time is too short, the effect of liquid phase sintering cannot be fully exerted, and the density of the material cannot meet the requirements. In the cooling process, cooling is required after sintering is completed. The control of cooling rate is also very important. The appropriate cooling rate can make the material's structure more uniform. For example, for some materials containing multiple phases, if the cooling rate is too fast, new internal stress may be generated, and even incomplete phase transformation may occur, affecting the performance of the material. Application areas of liquid phase sintering process: Preparation of cemented carbide. Cemented carbide such as WC-Co alloy can be tightly combined by liquid phase sintering to improve the hardness, wear resistance and toughness of the alloy. Ceramic material processing. Some ceramic materials such as silicon nitride (Si3N4) ceramics can adopt liquid phase sintering process. Adding appropriate flux during the sintering process to form a liquid phase helps to improve the densification of ceramics. Manufacturing of metal matrix composites. For metal matrix composites such as aluminum matrix composites (Al-SiC, etc.), liquid phase sintering can make the reinforcing phase (SiC particles, etc.) evenly distributed in the metal matrix, enhancing the mechanical properties of the material. This material has broad application prospects in the fields of electronic packaging and automotive parts.

[0036] Liquid phase sintering process refers to the sintering process of powder or compact with at least two components in a liquid phase state. Liquid phase sintering process has been widely used to manufacture various sintered alloy parts, electrical contact materials, cemented carbide and metal ceramics. Liquid phase sintering originates from powder metallurgy and refers to the sintering process in which liquid and solid phase particles coexist. At this time, the sintering temperature is higher than the melting point of the low melting component or low melting eutectic in the sintered body and lower than the melting point of the high melting point component. Since the liquid phase migration of the material is much faster than the solid phase diffusion, the densification rate and final density of the sintered body are greatly improved. Liquid phase sintering process is a sintering process with liquid phase generation. It can be divided into two categories: one is that the liquid phase exists throughout the sintering process, and the other is that the liquid phase disappears in the later stage of sintering. The liquid phase sintering process can be divided into the following four stages: pre-sintering stage, shrinkage stage, liquid phase sintering, cooling stage. Sintering in which a small part of the raw material becomes liquid. The alloy powder to be sintered (base phase alloy powder) is uniformly mixed with an appropriate alloy powder (liquid phase alloy powder) with a lower melting point. At the sintering temperature, the liquid phase alloy powder becomes liquid, which can increase the sintering densification rate and the density of the final product. The formation of the liquid phase is the result of the melting of the fusible components in the product at the sintering temperature. The liquid phase sintering speed is fast and the shrinkage is significant. After sintering, a product with a density close to the theoretical density can be obtained. During liquid phase sintering, it is necessary to ensure that an appropriate amount of liquid phase (15-35%) is generated. The liquid phase must have good wettability to the solid phase, and the solid phase must have a certain solubility in the liquid phase. Sintering method with liquid phase participation. The sintering temperature is lower than that of pure solid phase sintering. The sintered material generally contains multiple components and is sintered near the lowest eutectic point. Viscous flow mass transfer and dissolution precipitation mass transfer occur in the sintered material, which accelerates the sintering speed and thus reduces the sintering temperature. For this reason, when sintering pure compound ceramics, a small amount of flux is often added to the powder to achieve sintering at a lower temperature. According to the principle of liquid phase sintering, the densification of powder is achieved by arranging high melting point particles around low melting point components in the liquid phase. At present, various powders have been tested to study powder systems with good wettability, that is, the liquid phase formed by low melting point metal powder as a binder around the high melting point powder has been connected to obtain materials. Among them, the important alloy powder systems are copper-based powders and nickel-based powders. Sintering temperature is an important parameter of liquid phase sintering process. The liquid phase sintering process can be roughly divided into three stages: liquid phase generation and solid phase particle rearrangement stage; solid phase dissolution and precipitation stage; solid phase skeleton formation stage. In order for liquid phase sintering to proceed smoothly and obtain a dense hot pressing body, the following conditions must be met: the liquid phase should have good wettability to the solid phase at the hot pressing temperature; the liquid phase should have a certain solubility in the solid phase; the liquid phase should have a certain amount. Obviously, increasing the temperature increases the activity of atoms, which is conducive to the interface reaction of metal powders, thereby improving the wettability of the liquid phase to the solid phase; in addition, increasing the temperature will increase the liquid phase content. Therefore, increasing the sintering temperature will be conducive to the smooth progress of liquid phase sintering.It can be seen that a reasonable sintering temperature is a prerequisite for obtaining a dense sintered body with excellent performance.

[0037] The present invention proposes to prepare FeSi-Ni3Si / TiB2-TiC composite material blocks by using a molten metal liquid phase sintering process, that is, the melting points of FeSi intermetallic compounds and Ni3Si intermetallic compounds are lower than the sintering temperature. At a higher sintering temperature, FeSi metal and Ni3Si metal will melt to form a liquid phase, and the FeSi metal and Ni3Si metal are sintered together with TiB2 ceramics and TiC ceramics through a liquid phase sintering process to prepare a dense FeSi-Ni3Si / TiB2-TiC composite material block. The molten metal liquid phase sintering process has a low preparation process cost and good product performance. The molten metal liquid phase sintering process of the present invention only requires a vacuum high-temperature sintering furnace, and a vacuum high-temperature sintering furnace with a sintering temperature below 2000°C can be used. Since the vacuum high-temperature sintering furnace does not have a complex pressurization system, the equipment cost is relatively low. The molten metal liquid phase sintering process can simplify the production process and reduce production costs. It can also produce sintered products with complex shapes. The prepared FeSi-Ni3Si / TiB2-TiC composite material has high density and high mechanical properties as well as good wear resistance. BRIEF DESCRIPTION OF THE DRAWINGS

[0038] Figure 1 The X-ray diffraction spectrum of the FeSi-Ni3Si / TiB2-TiC composite material block prepared by the method of the present invention. DETAILED DESCRIPTION

[0039] The present invention is further described in detail below with reference to the accompanying drawings and embodiments.

[0040] Example 1

[0041] The molten metal liquid phase sintering process of the FeSi-Ni3Si / TiB2-TiC composite material comprises the following steps according to the mass fraction:

[0042] Step 1: Prepare Fe-Si intermetallic compound powder by mechanical alloying process. The specific steps are:

[0043] Fe-Si intermetallic compound powder is prepared by ball milling for 80 hours using a mechanical alloying process, wherein the ball milling jar is a polytetrafluoroethylene ball milling jar, the grinding balls are agate grinding balls, the mass ratio of the agate grinding balls to the mixed powder is 10:1, and the molar ratio of Fe powder to Si powder is 50:50; Fe powder and Si powder are loaded into the ball milling jar of a QM-1SP2 planetary ball mill, and the planetary ball mill is started after four ball milling jars are fixed for mechanical ball milling, the mechanical ball milling time is 80 hours, the speed of the ball mill is 400r / min, dry ball milling is adopted, and intermittent ball milling is adopted, argon gas is filled into the ball milling jar as a protective gas, and Fe-Si intermetallic compound powder is prepared by ball milling for 80 hours using a mechanical alloying process, the purity of the Fe powder is 99%, and the particle size is 75-85μm; the purity of the Si powder is 99%, and the particle size is 75-85μm;

[0044] Step 2: The Fe-Si intermetallic compound powder prepared in step 1 is subjected to a heat treatment process to prepare FeSi intermetallic compound powder. The specific steps are:

[0045] The Fe-Si intermetallic compound powder and 10 parts of phenolic resin binder are placed in a ball mill, and 300 ml of anhydrous ethanol and 30 agate grinding balls with a diameter of 15 mm are added and mechanically ball milled for 24 hours to prepare a slurry, which is then mixed by wet ball milling to prepare a slurry, and the slurry is placed in a glass beaker and the glass beaker is placed in an oven and dried at 100°C for 24 hours to prepare a mixed powder A, and the mixed powder A is placed in a steel mold that can be made into a strip sample, and is pressed into a strip sample by a pressure molding machine at a pressure of 100 MPa for a holding time of 3 minutes, the size of the strip sample is 50 mm×5 mm×6 mm, and the strip sample is placed in a graphite crucible, and the graphite crucible is placed in a vacuum sintering furnace, wherein the heat treatment temperature is 800°C, the holding time is 1 hour, and the vacuum degree is 10 -2 Pa, a heat treatment process is performed under vacuum conditions, and a FeSi intermetallic compound powder strip sample with a porous structure is obtained through the heat treatment process. After the heat treatment process is completed, the FeSi intermetallic compound strip sample is taken out, and then crushed and ground into FeSi intermetallic compound powder to obtain FeSi intermetallic compound powder; a small amount of phenolic resin is completely decomposed and volatilized during the high-temperature heat treatment process, and no phenolic resin remains in the obtained powder;

[0046] Step 3: Prepare Ni-Si intermetallic compound powder by mechanical alloying process. The specific steps are:

[0047] A Ni-Si intermetallic compound powder is prepared by ball milling for 80 hours using a mechanical alloying process, wherein a polytetrafluoroethylene ball mill is used for the ball mill, agate balls are used for the grinding balls, the mass ratio of the agate balls to the mixed powder is 10:1, and the molar ratio of the Ni powder to the Si powder is 75:25; Ni powder and Si powder are loaded into the ball mill of a QM-1SP2 planetary ball mill, and the planetary ball mill is started after four ball mills are fixed for mechanical ball milling, the mechanical ball milling time is 80 hours, the speed of the ball mill is 400r / min, dry ball milling is used, and intermittent ball milling is used, argon is filled into the ball mill as a protective gas, and a Ni-Si intermetallic compound powder is prepared by ball milling for 80 hours using a mechanical alloying process, wherein the purity of the Ni powder is 99%, and the particle size is 75-85μm; the purity of the Si powder is 99%, and the particle size is 75-85μm;

[0048] Step 4: The Ni-Si intermetallic compound powder prepared in step 3 is subjected to a heat treatment process to prepare Ni3Si intermetallic compound powder. The specific steps are:

[0049] The Ni-Si intermetallic compound powder and 10 parts of phenolic resin binder are placed in a ball mill, and 300 ml of anhydrous ethanol and 30 agate grinding balls with a diameter of 15 mm are added and mechanically ball milled for 24 hours to prepare a slurry, which is then mixed by wet ball milling to prepare a slurry, and the slurry is placed in a glass beaker and the glass beaker is placed in an oven and dried at 100°C for 24 hours to prepare a mixed powder B, and the mixed powder B is placed in a steel mold that can be made into a strip sample, and is pressed into a strip sample by a pressure molding machine at a pressure of 100 MPa for a holding time of 3 minutes, the size of the strip sample is 50 mm×5 mm×6 mm, and the strip sample is placed in a graphite crucible, and the graphite crucible is placed in a vacuum sintering furnace, wherein the heat treatment temperature is 800°C, the holding time is 1 hour, and the vacuum degree is 10 -2 Pa, a Ni3Si intermetallic compound powder strip sample with a porous structure is obtained through the heat treatment process, and after the heat treatment process, the Ni3Si intermetallic compound strip sample is taken out, and then crushed and ground into Ni3Si intermetallic compound powder to obtain Ni3Si intermetallic compound powder; a small amount of phenolic resin is completely decomposed and volatilized during the high-temperature heat treatment process, and no phenolic resin remains in the obtained powder;

[0050] Step 5: Mix 10 parts of the FeSi intermetallic compound powder and Ni3Si intermetallic compound powder prepared by steps 2 and 4 with 90 parts of the TiB2 powder and TiC powder, add 3 parts of Al2O3 powder and 7 parts of Y2O3 powder as sintering aids to the mixed powder to obtain a mixed powder C, put the obtained FeSi intermetallic compound powder and Ni3Si intermetallic compound powder into a ball mill, add 100 ml of anhydrous ethanol and 30 agate grinding balls with a diameter of 10 mm into the ball mill, and mix them by mechanical ball milling for 24 hours to prepare a slurry, put the slurry into a glass beaker, and put the glass beaker into an oven and dry it at 100°C for 24 hours to prepare a FeSi-Ni3Si / TiB2-TiC composite powder. The mass fractions of FeSi intermetallic compound powder and Ni3Si intermetallic compound powder in the FeSi-Ni3Si / TiB2-TiC composite powder are 10 parts, wherein the FeSi intermetallic compound powder and the Ni3Si intermetallic compound powder are 5 parts, the TiB2 ceramic powder is 45 parts and the TiC ceramic powder is 45 parts in the FeSi-Ni3Si / TiB2-TiC composite powder;

[0051] Step 6: The FeSi-Ni3Si / TiB2-TiC composite powder obtained in step 5 is mixed with 10 parts of phenolic resin binder to prepare a mixed powder, which is then loaded into a ball mill and added with 300 ml of anhydrous ethanol and 30 agate grinding balls with a diameter of 15 mm for mechanical ball milling for 24 hours to prepare a slurry, which is then mixed by wet ball milling to prepare a slurry, and the slurry is loaded into a glass beaker, and the glass beaker is placed in an oven and dried at 100°C for 24 hours to prepare a mixed powder D containing a phenolic resin binder, and the mixed powder D containing a small amount of phenolic resin binder is loaded into a steel mold for preparing a strip sample, and is pressed into a strip sample preform by a pressure molding machine at a pressure of 100 MPa for a holding time of 3 minutes, and the size of the strip sample preform is 50 mm×5 mm ×6mm, the strip sample preform is placed in a drying oven and dried at 150°C for 24h to completely solidify the phenolic resin, and a FeSi-Ni3Si / TiB2-TiC composite powder strip sample preform containing a phenolic resin binder with a certain strength is obtained, and the strip sample preform is put into a latex glove, wrapped with a latex glove, sealed and placed in a cold isostatic press, the medium in the cold isostatic press is hydraulic oil, and the holding time in the cold isostatic press is 5 minutes at a pressure of 100MPa. After the holding time, the sample is taken out and isostatically pressed by the cold isostatic press to form a dense FeSi-Ni3Si / TiB2-TiC composite powder strip sample preform, and the size of the strip sample preform is 50mm×5mm×6mm;

[0052] Step 7: Place the FeSi-Ni3Si / TiB2-TiC composite powder strip sample preformed body prepared by pressure forming in step 6 into a graphite crucible, and place the graphite crucible into a vacuum high-temperature sintering furnace for a molten metal liquid phase sintering process; the molten metal liquid phase sintering process is as follows: the sintering temperature is 1500°C, the holding time is 2h, and the molten metal liquid phase sintering process is carried out under vacuum conditions, and the vacuum degree is 10 -2 Pa; the heating rate during the sintering process is 10℃ / min. After the sintering process is completed, the furnace is cooled. The FeSi-Ni3Si / TiB2-TiC composite material block is prepared by the molten metal liquid phase sintering process. The melting point of the FeSi intermetallic compound is 1410°C, and the melting point of the Ni3Si intermetallic compound is 1255°C. When sintered at 1500°C, the FeSi intermetallic compound and the Ni3Si intermetallic compound will melt to form a liquid phase. The FeSi intermetallic compound liquid phase and the Ni3Si intermetallic compound liquid phase will infiltrate into the middle of the TiB2 particles and the TiC particles through the pores in the TiB2 matrix and the TiC matrix, so that the molten FeSi intermetallic compound liquid phase and the molten Ni3Si intermetallic compound liquid phase fill the pores in the TiB2 ceramic and the TiC ceramic matrix. Since the FeSi alloy liquid phase particles and the Ni3Si alloy liquid phase particles have good wettability with the TiB2 particles and the TiC particles, the FeSi intermetallic compound and the Ni3Si intermetallic compound can be well bonded with the TiB2 particles and the TiC particles to form a dense FeSi-Ni3Si / TiB2-TiC composite material sintered block. Moreover, the higher the content of FeSi alloy and Ni3Si alloy, the denser the FeSi-Ni3Si / TiB2-TiC composite material is. During the sintering process, Al2O3 powder and Y2O3 powder sintering aid react at high temperature to form liquid Y3Al5O 12 , namely YAG phase, forms a liquid phase to promote the densification of the ceramic composite matrix and improve the mechanical properties of the ceramic composite; the phenolic resin binder decomposes into gas at high temperature and evaporates, leaving only a small amount of residual carbon, which is mixed in the sintered sample. The FeSi-Ni3Si / TiB2-TiC composite block has high density and high mechanical properties. The total number of FeSi intermetallic compounds and Ni3Si intermetallic compounds in the FeSi-Ni3Si / TiB2-TiC composite is 10 parts.

[0053] Example 2

[0054] The molten metal liquid phase sintering process of the FeSi-Ni3Si / TiB2-TiC composite material comprises the following steps by weight:

[0055] Step 1: Prepare Fe-Si intermetallic compound powder by mechanical alloying process. The specific steps are:

[0056] The Fe-Si intermetallic compound powder is prepared by ball milling for 80 hours using a mechanical alloying process, wherein the ball milling jar is a polytetrafluoroethylene ball milling jar, the grinding balls are agate grinding balls, the mass ratio of the agate grinding balls to the mixed powder is 10:1, wherein the molar ratio of Fe powder to Si powder is 50:50, the Fe powder and Si powder are loaded into the ball milling jar of the QM-1SP2 planetary ball mill, and the planetary ball mill is started for mechanical ball milling after the four ball milling jars are fixed. The mechanical ball milling time is 80 hours, the speed of the ball mill is 400r / min, dry ball milling is adopted, and intermittent ball milling is adopted, and argon gas is filled in the ball milling jar as a protective gas. The Fe-Si intermetallic compound powder is prepared by ball milling for 80 hours using a mechanical alloying process, the purity of the Fe powder is 99%, and the particle size is 85-90μm; the purity of the Si powder is 99%, and the particle size is 85-90μm;

[0057] Step 2: The Fe-Si intermetallic compound powder prepared in step 1 is subjected to a heat treatment process to prepare FeSi intermetallic compound powder. The specific steps are:

[0058] The Fe-Si intermetallic compound powder and 10 parts of phenolic resin binder were placed in a ball mill, and 300 ml of anhydrous ethanol and 30 agate grinding balls with a diameter of 15 mm were added and mechanically ball milled for 24 hours to prepare a slurry, which was mixed by wet ball milling to prepare a slurry, and the slurry was placed in a glass beaker and dried in an oven at 100°C for 24 hours to prepare a mixed powder A, and the mixed powder A was placed in a steel mold capable of making a strip sample, and was pressed into a strip sample by a pressure molding machine at a pressure of 120 MPa for a holding time of 3 minutes, the size of the strip sample was 50 mm×5 mm×6 mm, and the strip sample was placed in a graphite crucible, and the graphite crucible was placed in a vacuum sintering furnace, wherein the heat treatment temperature was 900°C, the holding time was 1 hour, and the vacuum degree was 10 -2 Pa, a heat treatment process is performed under vacuum conditions, and a FeSi intermetallic compound powder strip sample with a porous structure is obtained through the heat treatment process. After the heat treatment is completed, the FeSi intermetallic compound strip sample is taken out, crushed and ground into FeSi intermetallic compound powder, and FeSi intermetallic compound powder is obtained; a small amount of phenolic resin is completely decomposed and volatilized during the high-temperature heat treatment process, and no phenolic resin remains in the obtained powder;

[0059] Step 3: Prepare Ni-Si intermetallic compound powder by mechanical alloying process. The specific steps are:

[0060] The Ni-Si intermetallic compound powder is prepared by ball milling for 80 hours using a mechanical alloying process, wherein the ball milling jar is a polytetrafluoroethylene ball milling jar, the grinding balls are agate grinding balls, the mass ratio of agate grinding balls to mixed powder is 10:1, and the molar ratio of Ni powder to Si powder is 75:25. Ni powder and Si powder are loaded into the ball milling jar of the QM-1SP2 planetary ball mill, and the planetary ball mill is started after four ball milling jars are fixed for mechanical ball milling; the mechanical ball milling time is 80 hours, the speed of the ball mill is 400r / min, dry ball milling is adopted, and intermittent ball milling is adopted, and argon is filled in the ball milling jar as a protective gas; Ni-Si intermetallic compound powder is prepared by ball milling for 80 hours using a mechanical alloying process; the purity of the Ni powder is 99%, and the particle size is 85-90μm; the purity of the Si powder is 99%, and the particle size is 85-90μm;

[0061] Step 4: The Ni-Si intermetallic compound powder prepared in step 3 is subjected to a heat treatment process to prepare Ni3Si intermetallic compound powder. The specific steps are:

[0062] The Ni-Si intermetallic compound powder and 10 parts of phenolic resin binder are placed in a ball mill, and 300 ml of anhydrous ethanol and 30 agate grinding balls with a diameter of 15 mm are added and mechanically ball milled for 24 hours to prepare a slurry, which is then mixed by wet ball milling to prepare a slurry, and the slurry is placed in a glass beaker and the glass beaker is placed in an oven and dried at 100°C for 24 hours to prepare a mixed powder B, and the mixed powder B is placed in a steel mold that can be made into a strip sample, and is pressed into a strip sample by a pressure molding machine at a pressure of 120 MPa for a holding time of 3 minutes, the size of the strip sample is 50 mm×5 mm×6 mm, and the strip sample is placed in a graphite crucible, and the graphite crucible is placed in a vacuum sintering furnace, wherein the heat treatment temperature is 900°C, the holding time is 1 hour, and the vacuum degree is 10 -2 Pa, a Ni3Si intermetallic compound powder strip sample with a porous structure is obtained through the heat treatment process, and after the heat treatment process, the Ni3Si intermetallic compound strip sample is taken out, crushed and ground into Ni3Si intermetallic compound powder, and Ni3Si intermetallic compound powder is obtained; a small amount of phenolic resin is completely decomposed and volatilized during the high-temperature heat treatment process, and no phenolic resin remains in the obtained powder;

[0063] Step 5: Mix 20 parts of the FeSi intermetallic compound powder and the Ni3Si intermetallic compound powder prepared in Step 2 and Step 4 with 80 parts of the TiB2 powder and the TiC powder, add 4 parts of Al2O3 powder and 6 parts of Y2O3 powder as sintering aids to the mixed powder to obtain mixed powder C, put the mixed powder C into a ball mill, add 150 ml of anhydrous ethanol and 35 agate grinding balls with a diameter of 11 mm into the ball mill, and perform mechanical ball milling for 24 hours to prepare a slurry, and put the slurry into a glass beaker and put the glass beaker into an oven and dry it at 100°C for 24h to prepare FeSi-Ni3Si / TiB2-TiC composite powder; wherein the total number of FeSi intermetallic compound powder and Ni3Si intermetallic compound powder in the FeSi-Ni3Si / TiB2-TiC composite powder is 20 parts; wherein the FeSi intermetallic compound powder and Ni3Si intermetallic compound powder are 10 parts in the FeSi-Ni3Si / TiB2-TiC composite powder; 40 parts of TiB2 ceramic powder and 40 parts of TiC ceramic powder;

[0064] Step six: The FeSi-Ni3Si / TiB2-TiC composite powder obtained in step five is mixed with 10 parts of phenolic resin binder, loaded into a ball mill, and 300 ml of anhydrous ethanol and 30 agate grinding balls with a diameter of 15 mm are added, and mechanical ball milling is performed for 24 hours to prepare a slurry, and the slurry is prepared by wet ball milling and the slurry is loaded into a glass beaker, and the glass beaker is placed in an oven and dried at 100°C for 24 hours to prepare a mixed powder D containing a phenolic resin binder, and the mixed powder D is loaded into a steel mold capable of making strip specimens, and is pressed into a strip specimen preform by a pressure molding machine at a pressure of 120 MPa for a holding time of 3 minutes, and the size of the strip specimen preform is 50 mm×5 mm×6 mm. The strip sample preform is placed in a drying oven and dried at 150°C for 24 hours to completely solidify the phenolic resin, and a FeSi-Ni3Si / TiB2-TiC composite powder strip sample preform containing a phenolic resin binder with a certain strength is obtained. The strip sample preform is placed in a latex glove, wrapped with a latex glove, sealed, and placed in a cold isostatic press. The medium in the cold isostatic press is hydraulic oil. The pressure is maintained at a pressure of 120MPa in the cold isostatic press for 5 minutes. After the pressure maintenance time, the sample is taken out to obtain a FeSi-Ni3Si / TiB2-TiC composite powder strip sample preform. The size of the strip sample preform is 50mm×5mm×6mm.

[0065] Step 7: Place the FeSi-Ni3Si / TiB2-TiC composite powder strip sample preformed body prepared by pressure forming in step 6 into a graphite crucible, and place the graphite crucible into a vacuum high-temperature sintering furnace for a molten metal liquid phase sintering process; the molten metal liquid phase sintering process preparation method is as follows: the sintering temperature is 1550°C, the holding time is 2h, and the molten metal liquid phase sintering process is carried out under vacuum conditions, and the vacuum degree is 10 -2 Pa. The heating rate during the sintering process is 15℃ / min. After the sintering process is completed, the furnace is cooled. FeSi-Ni3Si / TiB2-TiC composite block is prepared by molten metal liquid phase sintering process. The melting point of the FeSi intermetallic compound is 1410°C, and the melting point of the Ni3Si intermetallic compound is 1255°C. When sintered at 1550°C, the FeSi intermetallic compound and the Ni3Si intermetallic compound will melt to form a liquid phase. The FeSi intermetallic compound liquid phase and the Ni3Si intermetallic compound liquid phase will infiltrate into the middle of the TiB2 particles and the TiC particles through the pores in the TiB2 matrix and the TiC matrix, so that the molten FeSi intermetallic compound liquid phase and the molten Ni3Si intermetallic compound liquid phase fill the pores in the TiB2 ceramic and the TiC ceramic matrix. Since the FeSi alloy liquid phase particles and the Ni3Si alloy liquid phase particles have good wettability with the TiB2 particles and the TiC particles, the FeSi intermetallic compound and the Ni3Si intermetallic compound can be well bonded with the TiB2 particles and the TiC particles to form a dense FeSi-Ni3Si / TiB2-TiC composite material sintered block. Moreover, the higher the content of FeSi alloy and Ni3Si alloy, the denser the FeSi-Ni3Si / TiB2-TiC composite material is. During the sintering process, Al2O3 powder and Y2O3 powder sintering aid react at high temperature to form liquid Y3Al5O 12 , namely YAG phase, forms a liquid phase to promote the densification of the ceramic composite matrix and improve the mechanical properties of the ceramic composite. The phenolic resin binder decomposes into gas and evaporates at high temperature, leaving only a small amount of residual carbon, which is mixed in the sintered sample. The FeSi-Ni3Si / TiB2-TiC composite block has high density and high mechanical properties. The total number of FeSi intermetallic compounds and Ni3Si intermetallic compounds in the FeSi-Ni3Si / TiB2-TiC composite is 20 parts.

[0066] Example 3

[0067] The molten metal liquid phase sintering process of the FeSi-Ni3Si / TiB2-TiC composite material comprises the following steps by weight:

[0068] Step 1: Prepare Fe-Si intermetallic compound powder by mechanical alloying process. The specific steps are:

[0069] Fe-Si intermetallic compound powder was prepared by ball milling for 80 hours using a mechanical alloying process, wherein the ball milling jar was a polytetrafluoroethylene ball milling jar, the grinding balls were agate grinding balls, the mass ratio of agate grinding balls to mixed powder was 10:1, and the molar ratio of Fe powder to Si powder was 50:50. Fe powder and Si powder were loaded into the ball milling jar of QM-1SP2 planetary ball mill, and the four ball milling jars were fixed and then the planetary ball mill was started for mechanical ball milling. The mechanical ball milling time was 80 hours, the speed of the ball mill was 400r / min, dry ball milling was used, and intermittent ball milling was used. Argon was filled into the ball milling jar as a protective gas, and Fe-Si intermetallic compound powder was prepared by ball milling for 80 hours using a mechanical alloying process. The purity of the Fe powder was 99%, and the particle size was 90-100μm; the purity of the Si powder was 99%, and the particle size was 90-100μm;

[0070] Step 2: The Fe-Si intermetallic compound powder prepared in step 1 is subjected to a heat treatment process to prepare FeSi intermetallic compound powder. The specific steps are:

[0071] The Fe-Si intermetallic compound powder and 10 parts by mass of phenolic resin binder were placed in a ball mill, and 300 ml of anhydrous ethanol and 30 agate grinding balls with a diameter of 15 mm were added and mechanically ball milled for 24 hours to prepare a slurry, which was mixed by wet ball milling to prepare a slurry, and the slurry was placed in a glass beaker, and the glass beaker was placed in an oven and dried at 100°C for 24 hours to prepare a mixed powder A, and the mixed powder A was placed in a steel mold that can be made into a strip sample, and was pressed into a strip sample by a pressure molding machine at a pressure of 140 MPa for a holding time of 3 minutes, the size of the strip sample was 50 mm×5 mm×6 mm, and the strip sample was placed in a graphite crucible, and the graphite crucible was placed in a vacuum sintering furnace, wherein the heat treatment temperature was 1000°C, the holding time was 1 hour, and the vacuum degree was 10 -2 The heat treatment process is carried out under vacuum conditions of 1000 Pa, and a porous FeSi intermetallic compound powder strip sample is obtained through the heat treatment process. After the heat treatment process, the FeSi intermetallic compound strip sample is taken out, and then crushed and ground into FeSi intermetallic compound powder. FeSi intermetallic compound powder is prepared through the heat treatment process; a small amount of phenolic resin is completely decomposed and volatilized during the high-temperature heat treatment process, and no phenolic resin remains in the obtained powder;

[0072] Step 3: Prepare Ni-Si intermetallic compound powder by mechanical alloying process. The specific steps are:

[0073] The Ni-Si intermetallic compound powder was prepared by ball milling for 80 hours using a mechanical alloying process, wherein the ball milling jar is a polytetrafluoroethylene ball milling jar, the grinding balls are agate grinding balls, the mass ratio of agate grinding balls to mixed powder is 10:1, and the molar ratio of Ni powder to Si powder is 75:25. Ni powder and Si powder were loaded into the ball milling jar of the QM-1SP2 planetary ball mill, and the planetary ball mill was started for mechanical ball milling after the four ball milling jars were fixed. The mechanical ball milling time was 80 hours, the speed of the ball mill was 400r / min, dry ball milling was adopted, and intermittent ball milling was adopted, and argon was filled in the ball milling jar as a protective gas. Ni-Si intermetallic compound powder was prepared by ball milling for 80 hours using a mechanical alloying process. The purity of the Ni powder is 99%, and the particle size is 90-100μm; the purity of the Si powder is 99%, and the particle size is 90-100μm;

[0074] Step 4: The Ni-Si intermetallic compound powder prepared in step 3 is subjected to a heat treatment process to prepare Ni3Si intermetallic compound powder. The specific steps are:

[0075] The Ni-Si intermetallic compound powder and 10 parts of phenolic resin binder are placed in a ball mill, and 300 ml of anhydrous ethanol and 30 agate grinding balls with a diameter of 15 mm are added and mechanically ball milled for 24 hours to prepare a slurry, which is then mixed by wet ball milling to prepare a slurry. The slurry is placed in a glass beaker and dried in an oven at 100°C for 24 hours to prepare a mixed powder B, and the mixed powder B is placed in a steel mold that can be made into a strip sample, and is pressed into a strip sample by a pressure molding machine at a pressure of 140 MPa for a holding time of 3 minutes, the size of the strip sample is 50 mm×5 mm×6 mm, and the strip sample is placed in a graphite crucible, and the graphite crucible is placed in a vacuum sintering furnace, wherein the heat treatment temperature is 1000°C, the holding time is 1 hour, and the vacuum degree is 10 -2 Pa, a Ni3Si intermetallic compound powder strip sample with a porous structure is obtained, and after the heat treatment, the Ni3Si intermetallic compound strip sample is taken out, crushed and ground into Ni3Si intermetallic compound powder, and Ni3Si intermetallic compound powder is obtained; a small amount of phenolic resin is completely decomposed and volatilized during the high-temperature heat treatment process, and no phenolic resin remains in the obtained powder;

[0076] Step 5: Mix 30 parts by weight of the FeSi intermetallic compound powder and the Ni3Si intermetallic compound powder prepared in Steps 2 and 4 with 70 parts by weight of the TiB2 powder and the TiC powder, add 5 parts by weight of Al2O3 powder and 5 parts by weight of Y2O3 powder as sintering aids to the mixed powder to obtain a mixed powder C, and put the obtained FeSi intermetallic compound powder and the Ni3Si intermetallic compound powder, the TiB2 powder and the TiC powder, and the Al2O3 powder and the Y2O3 powder sintering aids into a ball mill, and add 200 ml of anhydrous Ethanol and 40 agate grinding balls with a diameter of 12 mm are mechanically ball-milled for 24 hours to prepare a slurry, and the slurry is put into a glass beaker and the glass beaker is placed in an oven and dried at 100°C for 24 hours to prepare a FeSi-Ni3Si / TiB2-TiC composite powder; wherein the FeSi intermetallic compound powder and the Ni3Si intermetallic compound powder are 30 parts in the FeSi-Ni3Si / TiB2-TiC composite powder; wherein the FeSi intermetallic compound powder and the Ni3Si intermetallic compound powder are 15 parts in the FeSi-Ni3Si / TiB2-TiC composite powder; the TiB2 ceramic powder is 35 parts and the TiC ceramic powder is 35 parts;

[0077] Step 6: The FeSi-Ni3Si / TiB2-TiC composite powder obtained in step 5 is mixed with 10 parts of phenolic resin binder and then loaded into a ball mill and added with 300 ml of anhydrous ethanol and 30 agate grinding balls with a diameter of 15 mm for mechanical ball milling for 24 hours to prepare a slurry, which is then mixed by wet ball milling to prepare a slurry and loaded into a glass beaker and the glass beaker is placed in an oven and dried at 100°C for 24 hours to prepare a mixed powder D containing a phenolic resin binder, and the mixed powder D is loaded into a steel mold capable of making a strip sample, and is pressed into a strip sample preform by a pressure forming machine at a pressure of 140 MPa for a holding time of 3 minutes, and the size of the strip sample preform is 50 mm×5 m m×6mm; placing the strip sample preform in a drying oven and drying at 150°C for 24h to completely solidify the phenolic resin, thereby obtaining a FeSi-Ni3Si / TiB2-TiC composite powder strip sample preform containing a phenolic resin binder having a certain strength; placing the strip sample preform into a latex glove, wrapping it with the latex glove, sealing it, and placing it into a cold isostatic press, wherein the medium in the cold isostatic press is hydraulic oil, and the holding time in the cold isostatic press is 5 minutes at a pressure of 140MPa. After the holding time, the sample is taken out to obtain a FeSi-Ni3Si / TiB2-TiC composite powder strip sample preform, wherein the size of the strip sample preform is 50mm×5mm×6mm;

[0078] Step 7: Place the FeSi-Ni3Si / TiB2-TiC composite powder strip sample preformed body prepared by pressure forming in step 6 into a graphite crucible, and place the graphite crucible into a vacuum high-temperature sintering furnace for a molten metal liquid phase sintering process; the molten metal liquid phase sintering process is as follows: the sintering temperature is 1600°C, the holding time is 2h, and the molten metal liquid phase sintering process is carried out under vacuum conditions, and the vacuum degree is 10 -2 Pa. The heating rate during the sintering process was 20℃ / min, and the furnace was cooled after the sintering process. FeSi-Ni3Si / TiB2-TiC composite block was prepared by molten metal liquid phase sintering process. The melting point of the FeSi intermetallic compound is 1410°C, and the melting point of the Ni3Si intermetallic compound is 1255°C. When sintered at 1600°C, the FeSi intermetallic compound and the Ni3Si intermetallic compound will melt to form a liquid phase. The FeSi intermetallic compound liquid phase and the Ni3Si intermetallic compound liquid phase will infiltrate into the middle of the TiB2 particles and the TiC particles through the pores in the TiB2 matrix and the TiC matrix, so that the molten FeSi intermetallic compound liquid phase and the molten Ni3Si intermetallic compound liquid phase fill the pores in the TiB2 ceramic and the TiC ceramic matrix. Since the FeSi alloy liquid phase particles and the Ni3Si alloy liquid phase particles have good wettability with the TiB2 particles and the TiC particles, the FeSi intermetallic compound and the Ni3Si intermetallic compound can be well bonded with the TiB2 particles and the TiC particles to form a dense FeSi-Ni3Si / TiB2-TiC composite material sintered block. Moreover, the higher the content of FeSi alloy and Ni3Si alloy, the denser the FeSi-Ni3Si / TiB2-TiC composite material is. During the sintering process, Al2O3 powder and Y2O3 powder sintering aid react at high temperature to form liquid Y3Al5O 12 , namely YAG phase, forms a liquid phase to promote the densification of the ceramic composite matrix and improve the mechanical properties of the ceramic composite; while the phenolic resin binder decomposes into gas at high temperature and evaporates, leaving only a small amount of residual carbon, which is mixed in the sintered sample. The FeSi-Ni3Si / TiB2-TiC composite block has high density and high mechanical properties. The total number of FeSi intermetallic compounds and Ni3Si intermetallic compounds in the FeSi-Ni3Si / TiB2-TiC composite is 30 parts.

[0079] Example 4

[0080] The molten metal liquid phase sintering process of the FeSi-Ni3Si / TiB2-TiC composite material comprises the following steps by weight:

[0081] Step 1: Prepare Fe-Si intermetallic compound powder by mechanical alloying process. The specific steps are:

[0082] Fe-Si intermetallic compound powder was prepared by ball milling for 80 hours using a mechanical alloying process, wherein the ball milling jar was a polytetrafluoroethylene ball milling jar, the grinding balls were agate grinding balls, the mass ratio of agate grinding balls to mixed powder was 10:1, and the molar ratio of Fe powder to Si powder was 50:50. Fe powder and Si powder were loaded into the ball milling jar of the QM-1SP2 planetary ball mill, and the planetary ball mill was started for mechanical ball milling after four ball milling jars were fixed. The mechanical ball milling time was 80 hours, the speed of the ball mill was 400r / min, dry ball milling was adopted, and intermittent ball milling was adopted. Argon was filled into the ball milling jar as a protective gas, and Fe-Si intermetallic compound powder was prepared by ball milling for 80 hours using a mechanical alloying process; the purity of the Fe powder was 99%, and the particle size was 75-100μm; the purity of the Si powder was 99%, and the particle size was 75-100μm;

[0083] Step 2: The Fe-Si intermetallic compound powder prepared in step 1 is subjected to a heat treatment process to prepare FeSi intermetallic compound powder. The specific steps are:

[0084] The Fe-Si intermetallic compound powder and 10 parts by mass of phenolic resin binder were placed in a ball mill, and 300 ml of anhydrous ethanol and 30 agate grinding balls with a diameter of 15 mm were added and mechanically ball milled for 24 hours to prepare a slurry, which was mixed by wet ball milling to prepare a slurry, and the slurry was placed in a glass beaker and dried in an oven at 100°C for 24 hours to prepare a mixed powder A, and the mixed powder A was placed in a steel mold capable of making strip samples, and was pressed into a strip sample by a pressure molding machine at a pressure of 150 MPa for a holding time of 3 minutes, and the size of the strip sample was 50 mm×5 mm×6 mm, and the strip sample was placed in a graphite crucible, and then the graphite crucible was placed in a vacuum sintering furnace, wherein the heat treatment temperature was 1050°C, the holding time was 1 hour, and the vacuum degree was 10 -2 Pa, a heat treatment process is performed under vacuum conditions, and a FeSi intermetallic compound powder strip sample with a porous structure is obtained through the heat treatment process. After the heat treatment process is completed, the FeSi intermetallic compound strip sample is taken out, crushed and ground into FeSi intermetallic compound powder, and FeSi intermetallic compound powder is obtained; a small amount of phenolic resin is completely decomposed and volatilized during the high-temperature heat treatment process, and no phenolic resin remains in the obtained powder;

[0085] Step 3: Prepare Ni-Si intermetallic compound powder by mechanical alloying process. The specific steps are:

[0086] The Ni-Si intermetallic compound powder was prepared by ball milling for 80 hours using a mechanical alloying process, wherein the ball milling jar is a polytetrafluoroethylene ball milling jar, the grinding balls are agate grinding balls, the mass ratio of agate grinding balls to mixed powder is 10:1, and the molar ratio of Ni powder to Si powder is 75:25. Ni powder and Si powder are loaded into the ball milling jar of the QM-1SP2 planetary ball mill, and the planetary ball mill is started for mechanical ball milling after four ball milling jars are fixed. The mechanical ball milling time is 80 hours, the speed of the ball mill is 400r / min, dry ball milling is adopted, and intermittent ball milling is adopted. Argon is filled in the ball milling jar as a protective gas. Ni-Si intermetallic compound powder is prepared by ball milling for 80 hours using a mechanical alloying process; the purity of the Ni powder is 99%, and the particle size is 75-100μm; the purity of the Si powder is 99%, and the particle size is 75-100μm;

[0087] Step 4: The Ni-Si intermetallic compound powder prepared in step 3 is subjected to a heat treatment process to prepare Ni3Si intermetallic compound powder. The specific steps are:

[0088] The Ni-Si intermetallic compound powder and 10 parts of phenolic resin binder are placed in a ball mill, and 300 ml of anhydrous ethanol and 30 agate grinding balls with a diameter of 15 mm are added and mechanically ball milled for 24 hours to prepare a slurry, which is mixed by wet ball milling to prepare a slurry, and the slurry is placed in a glass beaker and dried in an oven at 100°C for 24 hours to prepare a mixed powder B, and the mixed powder B is placed in a steel mold that can be made into a strip sample, and is pressed into a strip sample by a pressure molding machine at a pressure of 150 MPa for a holding time of 3 minutes, and the size of the strip sample is 50 mm×5 mm×6 mm, and the strip sample is placed in a graphite crucible, and then the graphite crucible is placed in a vacuum sintering furnace, wherein the heat treatment temperature is 1050°C, the holding time is 1 hour, and the vacuum degree is 10 -2 Pa, a Ni3Si intermetallic compound powder strip sample with a porous structure is obtained, and after the heat treatment process, the Ni3Si intermetallic compound strip sample is taken out, crushed and ground into Ni3Si intermetallic compound powder, and Ni3Si intermetallic compound powder is obtained; a small amount of phenolic resin is completely decomposed and volatilized during the high-temperature heat treatment process, and no phenolic resin remains in the obtained powder;

[0089] Step 5: Mix 40 parts of the FeSi intermetallic compound powder and the Ni3Si intermetallic compound powder prepared in step 2 and step 4 with 60 parts of the TiB2 powder and the TiC powder, add 6 parts of Al2O3 powder and 4 parts of Y2O3 powder as sintering aids to the mixed powder to obtain a mixed powder C, put the obtained FeSi intermetallic compound powder and the Ni3Si intermetallic compound powder, the TiB2 powder and the TiC powder, and the Al2O3 powder and the Y2O3 powder sintering aids into a ball mill, and add 250 ml of anhydrous ethanol to the ball mill. and 45 agate grinding balls with a diameter of 13 mm were mechanically ball-milled for 24 hours to prepare a slurry, and the slurry was put into a glass beaker and dried in an oven at 100°C for 24 hours to prepare a FeSi-Ni3Si / TiB2-TiC composite powder; the total number of FeSi intermetallic compound powder and Ni3Si intermetallic compound powder in the FeSi-Ni3Si / TiB2-TiC composite powder was 40 parts; the FeSi intermetallic compound powder and the Ni3Si intermetallic compound powder were 20 parts in the FeSi-Ni3Si / TiB2-TiC composite powder; the TiB2 ceramic powder was 30 parts and the TiC ceramic powder was 30 parts;

[0090] Step 6: The FeSi-Ni3Si / TiB2-TiC composite powder obtained in step 5 is mixed with 10 parts of phenolic resin binder and then put into a ball mill and add 300 ml of anhydrous ethanol and 30 agate grinding balls with a diameter of 15 mm for mechanical ball milling for 24 hours to prepare a slurry, which is then mixed by wet ball milling to prepare a slurry. The slurry is put into a glass beaker and dried in an oven at 100°C for 24 hours to prepare a mixed powder D containing a phenolic resin binder. The mixed powder D is put into a steel mold for preparing a strip sample, and a strip sample preform is prepared by a pressure molding machine at a pressure of 150 MPa for a holding time of 3 minutes. The size of the strip sample preform is 50 mm×5 mm×6 mm; the strip sample The sample preform is placed in a drying oven and dried at 150° C. for 24 hours to completely solidify the phenolic resin, and a FeSi-Ni3Si / TiB2-TiC composite powder strip sample preform containing a phenolic resin binder having a certain strength is obtained. The strip sample preform is put into a latex glove, wrapped and sealed with a latex glove, and placed in a cold isostatic press. The medium in the cold isostatic press is hydraulic oil. The holding time in the cold isostatic press is 5 minutes at a pressure of 150 MPa. After the holding time, the sample is taken out to obtain a dense FeSi-Ni3Si / TiB2-TiC composite powder strip sample preform. The size of the strip sample preform is 50 mm×5 mm×6 mm.

[0091] Step 7: Place the FeSi-Ni3Si / TiB2-TiC composite powder strip sample preformed body prepared by pressure forming in step 6 into a graphite crucible, and place the graphite crucible into a vacuum high-temperature sintering furnace for a molten metal liquid phase sintering process; the molten metal liquid phase sintering process is as follows: the sintering temperature is 1650°C, the holding time is 2h, and the molten metal liquid phase sintering process is carried out under vacuum conditions, and the vacuum degree is 10 -2 Pa, the heating rate during the sintering process is 25℃ / min, and the furnace is cooled after the sintering process. FeSi-Ni3Si / TiB2-TiC composite block is prepared by molten metal liquid phase sintering process. The melting point of FeSi intermetallic compound is 1410℃, and the melting point of Ni3Si intermetallic compound is 1255℃. When sintered at 1650℃, FeSi intermetallic compound and Ni3Si intermetallic compound will melt to form liquid phase. The FeSi intermetallic compound liquid phase and Ni3Si intermetallic compound liquid phase will penetrate through the pores in the TiB2 matrix and the TiC matrix into the middle of the TiB2 particles and the TiC particles, so that the molten FeSi intermetallic compound liquid phase and the molten Ni3Si intermetallic compound liquid phase fill the pores in the TiB2 ceramic and TiC ceramic matrices. The wettability of gold liquid phase particles and Ni3Si alloy liquid phase particles with TiB2 particles and TiC particles is good. FeSi intermetallic compounds and Ni3Si intermetallic compounds can be well bonded with TiB2 particles and TiC particles to form dense FeSi-Ni3Si / TiB2-TiC composite sintered blocks. The higher the content of FeSi alloy and Ni3Si alloy, the denser the FeSi-Ni3Si / TiB2-TiC composite material. During the sintering process, Al2O3 powder and Y2O3 powder sintering aids react at high temperature to form liquid Y3Al5O 12 , namely YAG phase, forming a liquid phase to promote the densification of the ceramic composite matrix and improve the mechanical properties of the ceramic composite. The phenolic resin binder decomposes into gas at high temperature and evaporates, leaving only a small amount of residual carbon, which is mixed in the sintered sample. The FeSi-Ni3Si / TiB2-TiC composite block has a higher density and higher mechanical properties, and the total number of FeSi intermetallic compounds and Ni3Si intermetallic compounds in the FeSi-Ni3Si / TiB2-TiC composite is 40 parts.

[0092] Example 5

[0093] The molten metal liquid phase sintering process of the FeSi-Ni3Si / TiB2-TiC composite material comprises the following steps by weight:

[0094] Step 1: Prepare Fe-Si intermetallic compound powder by mechanical alloying process. The specific steps are:

[0095] Fe-Si intermetallic compound powder was prepared by ball milling for 80 hours using a mechanical alloying process, wherein the ball milling jar was a polytetrafluoroethylene ball milling jar, the grinding balls were agate grinding balls, the mass ratio of agate grinding balls to mixed powder was 10:1, and the molar ratio of Fe powder to Si powder was 50:50. Fe powder and Si powder were loaded into the ball milling jar of the QM-1SP2 planetary ball mill, and the planetary ball mill was started for mechanical ball milling after four ball milling jars were fixed. The mechanical ball milling time was 80 hours, the speed of the ball mill was 400r / min, dry ball milling was adopted, and intermittent ball milling was adopted. Argon was filled into the ball milling jar as a protective gas, and Fe-Si intermetallic compound powder was prepared by ball milling for 80 hours using a mechanical alloying process; the purity of the Fe powder was 99%, and the particle size was 75-100μm; the purity of the Si powder was 99%, and the particle size was 75-100μm;

[0096] Step 2: The Fe-Si intermetallic compound powder prepared in step 1 is subjected to a heat treatment process to prepare FeSi intermetallic compound powder. The specific steps are:

[0097] The Fe-Si intermetallic compound powder and 10 parts of phenolic resin binder are placed in a ball mill, and 300 ml of anhydrous ethanol and 30 agate grinding balls with a diameter of 15 mm are added and mechanically ball milled for 24 hours to prepare a slurry, which is then mixed by wet ball milling to prepare a slurry. The slurry is placed in a glass beaker and dried in an oven at 100°C for 24 hours to prepare a mixed powder A, and the mixed powder A is placed in a steel mold that can be made into a strip sample, and is pressed into a strip sample by a pressure molding machine at a pressure of 160 MPa for a holding time of 3 minutes. The size of the strip sample is 50 mm×5 mm×6 mm, and the strip sample is placed in a graphite crucible, and the graphite crucible is placed in a vacuum sintering furnace at a heat treatment temperature of 1100°C for 1 hour. -2 Pa, to obtain a porous and loose FeSi intermetallic compound powder strip sample, after the heat treatment, take out the FeSi intermetallic compound strip sample, crush and grind it into FeSi intermetallic compound powder, and obtain FeSi intermetallic compound powder; a small amount of phenolic resin is completely decomposed and volatilized during the high temperature heat treatment process, and no phenolic resin remains in the obtained powder;

[0098] Step 3: Prepare Ni-Si intermetallic compound powder by mechanical alloying process. The specific steps are:

[0099] A Ni-Si intermetallic compound powder is prepared by ball milling for 80 hours using a mechanical alloying process, wherein a polytetrafluoroethylene ball mill is used as a ball mill, agate balls are used as grinding balls, the mass ratio of agate balls to mixed powder is 10:1, wherein the molar ratio of Ni powder to Si powder is 75:25, Ni powder and Si powder are loaded into a ball mill of a QM-1SP2 planetary ball mill, four ball mills are fixed and then the planetary ball mill is started for mechanical ball milling, the mechanical ball milling time is 80 hours, the speed of the ball mill is 400r / min, dry ball milling is adopted, and intermittent ball milling is adopted, argon is filled into the ball mill as a protective gas, and a Ni-Si intermetallic compound powder is prepared by ball milling for 80 hours using a mechanical alloying process, wherein the purity of the Ni powder is 99% and the particle size is 75-100μm; the purity of the Si powder is 99% and the particle size is 75-100μm;

[0100] Step 4: The Ni-Si intermetallic compound powder prepared in step 3 is subjected to a heat treatment process to prepare Ni3Si intermetallic compound powder. The specific steps are:

[0101] The Ni-Si intermetallic compound powder and 10 parts of phenolic resin binder were placed in a ball mill, and 300 ml of anhydrous ethanol and 30 agate grinding balls with a diameter of 15 mm were added and mechanically ball milled for 24 hours to prepare a slurry, which was mixed by wet ball milling to prepare a slurry, and the slurry was placed in a glass beaker and dried in an oven at 100°C for 24 hours to prepare a mixed powder B, and the mixed powder B was placed in a steel mold capable of making a strip sample, and was pressed into a strip sample by a pressure molding machine at a pressure of 160 MPa for a holding time of 3 minutes, the size of the strip sample was 50 mm×5 mm×6 mm, and the strip sample was placed in a graphite crucible and heat treated in a vacuum sintering furnace at a heat treatment temperature of 1100°C for 1 hour, and at a vacuum degree of 10 -2 Pa, to obtain a porous and loose Ni3Si intermetallic compound powder strip sample, after the heat treatment, take out the Ni3Si intermetallic compound strip sample, crush and grind it into Ni3Si intermetallic compound powder, and obtain Ni3Si intermetallic compound powder; a small amount of phenolic resin is completely decomposed and volatilized during the high temperature heat treatment, and no phenolic resin remains in the obtained powder;

[0102] Step 5: Mix 50 parts of the FeSi intermetallic compound powder and Ni3Si intermetallic compound powder prepared in step 2 and step 4 with 50 parts of the TiB2 powder and TiC powder, add 7 parts of Al2O3 powder and 3 parts of Y2O3 powder as sintering aids to the mixed powder to obtain mixed powder C, put the obtained FeSi intermetallic compound powder and Ni3Si intermetallic compound powder, TiB2 powder and TiC powder, and the mixed powder C composed of Al2O3 powder and Y2O3 powder sintering aids into a ball mill, add 300 ml of anhydrous ethanol and 50 straight The slurry was prepared by mechanical ball milling with an agate grinding ball with a diameter of 14 mm for 24 hours, and the slurry was put into a glass beaker and dried in an oven at 100°C for 24 hours to prepare FeSi-Ni3Si / TiB2-TiC composite powder, wherein the FeSi intermetallic compound powder and the Ni3Si intermetallic compound powder accounted for 50 parts in the FeSi-Ni3Si / TiB2-TiC composite powder; the FeSi intermetallic compound powder accounted for 25 parts and the Ni3Si intermetallic compound powder accounted for 25 parts in the FeSi-Ni3Si / TiB2-TiC composite powder; the TiB2 ceramic powder accounted for 25 parts and the TiC ceramic powder accounted for 25 parts;

[0103] Step 6: The FeSi-Ni3Si / TiB2-TiC composite powder obtained in step 5 is mixed with 10 parts by mass of a phenolic resin binder and then placed in a ball mill jar, and 300 ml of anhydrous ethanol and 30 agate grinding balls with a diameter of 15 mm are added for mechanical ball milling for 24 hours to prepare a slurry, and the slurry is prepared by wet ball milling and the slurry is placed in a glass beaker, and the glass beaker is placed in an oven and dried at 100°C for 24 hours to prepare a mixed powder D containing a phenolic resin binder, and the mixed powder D is placed in a steel mold capable of making a strip sample, and is pressed into a strip sample preform by a pressure molding machine at a pressure of 160 MPa for a holding time of 3 minutes, and the size of the strip sample preform is 50 mm× 5mm×6mm, the strip sample preform is placed in a drying oven at 150°C and dried for 24h to completely solidify the phenolic resin, and a FeSi-Ni3Si / TiB2-TiC composite powder strip sample preform containing a phenolic resin binder with a certain strength is obtained, the strip sample preform is put into latex gloves, wrapped with latex gloves and sealed, and placed in a cold isostatic press, the medium in the cold isostatic press is hydraulic oil, and the holding time at a pressure of 160MPa in the cold isostatic press is 5 minutes, and the sample is taken out after the holding time ends to obtain a dense FeSi-Ni3Si / TiB2-TiC composite powder strip sample preform, and the size of the strip sample preform is 50mm×5mm×6mm;

[0104] Step 7: Place the FeSi-Ni3Si / TiB2-TiC composite powder strip sample preformed body prepared by pressure forming in step 6 into a graphite crucible, and place the graphite crucible into a vacuum high-temperature sintering furnace for a molten metal liquid phase sintering process; the molten metal liquid phase sintering process is as follows: the sintering temperature is 1700°C, the holding time is 2h, and the molten metal liquid phase sintering process is carried out under vacuum conditions, and the vacuum degree is 10 -2 Pa; the heating rate during the sintering process is 30℃ / min, and the furnace is cooled after the sintering process. FeSi-Ni3Si / TiB2-TiC composite block is prepared by molten metal liquid phase sintering process. The melting point of the FeSi intermetallic compound is 1410°C, and the melting point of the Ni3Si intermetallic compound is 1255°C. When sintered at 1700°C, the FeSi intermetallic compound and the Ni3Si intermetallic compound will melt to form a liquid phase. The FeSi intermetallic compound liquid phase and the Ni3Si intermetallic compound liquid phase will infiltrate into the middle of the TiB2 particles and the TiC particles through the pores in the TiB2 matrix and the TiC matrix, so that the molten FeSi intermetallic compound liquid phase and the molten Ni3Si intermetallic compound liquid phase will fill the pores in the TiB2 ceramic and the TiC ceramic matrix. Since the FeSi alloy liquid phase particles and the Ni3Si alloy liquid phase particles have good wettability with the TiB2 particles and the TiC particles, the FeSi intermetallic compound and the Ni3Si intermetallic compound can be well bonded with the TiB2 particles and the TiC particles to form a dense FeSi-Ni3Si / TiB2-TiC composite material sintered block. Moreover, the higher the content of FeSi alloy and Ni3Si alloy, the denser the FeSi-Ni3Si / TiB2-TiC composite material is. During the sintering process, Al2O3 powder and Y2O3 powder sintering aid react at high temperature to form liquid Y3Al5O 12 , namely YAG phase, forms a liquid phase to promote the densification of the ceramic composite matrix and improve the mechanical properties of the ceramic composite. The phenolic resin binder decomposes into gas at high temperature and evaporates, leaving only a small amount of residual carbon, which is mixed in the sintered sample. The FeSi-Ni3Si / TiB2-TiC composite block has high density and high mechanical properties. The total number of FeSi intermetallic compounds and Ni3Si intermetallic compounds in the FeSi-Ni3Si / TiB2-TiC composite is 50 parts.

[0105] Example 6

[0106] The molten metal liquid phase sintering process of the FeSi-Ni3Si / TiB2-TiC composite material comprises the following steps by weight:

[0107] Step 1: Prepare Fe-Si intermetallic compound powder by mechanical alloying process. The specific steps are:

[0108] Fe-Si intermetallic compound powder is prepared by ball milling for 80 hours using a mechanical alloying process, a polytetrafluoroethylene ball milling jar is used, agate grinding balls are used, the mass ratio of agate grinding balls to mixed powder is 10:1, wherein the molar ratio of Fe powder to Si powder is 50:50, Fe powder and Si powder are loaded into the ball milling jar of a QM-1SP2 planetary ball mill, and after fixing four ball mills, the planetary ball mill is started for mechanical ball milling, the mechanical ball milling time is 80 hours, the ball mill speed is 400r / min, dry ball milling is adopted, and intermittent ball milling is adopted, argon gas is filled into the ball milling jar as a protective gas, and Fe-Si intermetallic compound powder is prepared by ball milling for 80 hours using a mechanical alloying process; the purity of the Fe powder is 99%, and the particle size is 75-100μm; the purity of the Si powder is 99%, and the particle size is 75-100μm;

[0109] Step 2: The Fe-Si intermetallic compound powder prepared in step 1 is subjected to a heat treatment process to prepare FeSi intermetallic compound powder. The specific steps are:

[0110] The Fe-Si intermetallic compound powder and 10 parts of phenolic resin binder are placed in a ball mill, and 300 ml of anhydrous ethanol and 30 agate grinding balls with a diameter of 15 mm are added and mechanically ball milled for 24 hours to prepare a slurry, which is then mixed by wet ball milling to prepare a slurry, and the slurry is placed in a glass beaker and dried in an oven at 100°C for 24 hours to prepare a mixed powder A, which is placed in a steel mold capable of making strip samples, and is pressed into a strip sample by a pressure molding machine at a pressure of 180 MPa for a holding time of 3 minutes, the size of the strip sample is 50 mm×5 mm×6 mm, the strip sample is placed in a graphite crucible, and the graphite crucible is placed in a vacuum sintering furnace, the heat treatment temperature is 1150°C, the holding time is 1 hour, and the vacuum degree is 10 -2 Pa, to obtain a porous and loose FeSi intermetallic compound powder strip sample, after the heat treatment, take out the FeSi intermetallic compound strip sample, crush and grind it into FeSi intermetallic compound powder, and obtain FeSi intermetallic compound powder; a small amount of phenolic resin is completely decomposed and volatilized during the high temperature heat treatment process, and no phenolic resin remains in the obtained powder;

[0111] Step 3: Prepare Ni-Si intermetallic compound powder by mechanical alloying process. The specific steps are:

[0112] The Ni-Si intermetallic compound powder was prepared by ball milling for 80 hours using a mechanical alloying process, wherein the ball milling jar is a polytetrafluoroethylene ball milling jar, the grinding balls are agate grinding balls, the mass ratio of agate grinding balls to mixed powder is 10:1, and the molar ratio of Ni powder to Si powder is 75:25. Ni powder and Si powder are loaded into the ball milling jar of the QM-1SP2 planetary ball mill, and the planetary ball mill is started for mechanical ball milling after four ball milling jars are fixed. The mechanical ball milling time is 80 hours, the speed of the ball mill is 400r / min, dry ball milling is adopted, and intermittent ball milling is adopted. Argon is filled in the ball milling jar as a protective gas. Ni-Si intermetallic compound powder is prepared by ball milling for 80 hours using a mechanical alloying process; the purity of the Ni powder is 99%, and the particle size is 75-100μm; the purity of the Si powder is 99%, and the particle size is 75-100μm;

[0113] Step 4: The Ni-Si intermetallic compound powder prepared in step 3 is subjected to a heat treatment process to prepare Ni3Si intermetallic compound powder. The specific steps are:

[0114] The Ni-Si intermetallic compound powder and 10 parts of phenolic resin binder are placed in a ball mill, and 300 ml of anhydrous ethanol and 30 agate grinding balls with a diameter of 15 mm are added and mechanically ball milled for 24 hours to prepare a slurry, which is mixed by wet ball milling to prepare a slurry, and the slurry is placed in a glass beaker and dried in an oven at 100°C for 24 hours to prepare a mixed powder B, and the mixed powder B is placed in a steel mold that can be made into a strip sample, and is pressed into a strip sample by a pressure molding machine at a pressure of 180 MPa for a holding time of 3 minutes. The size of the strip sample is 50 mm×5 mm×6 mm, and the strip sample is placed in a graphite crucible, and the graphite crucible is placed in a vacuum sintering furnace. The heat treatment temperature is 1150°C, the holding time is 1 hour, and the vacuum degree is 10 -2 Pa, to obtain a porous and loose Ni3Si intermetallic compound powder strip sample, after the heat treatment, take out the Ni3Si intermetallic compound strip sample, crush and grind it into Ni3Si intermetallic compound powder, and obtain Ni3Si intermetallic compound powder; wherein a small amount of phenolic resin is completely decomposed and volatilized during the high temperature heat treatment process, and no phenolic resin remains in the obtained powder;

[0115] Step 5: Mix 60 parts of FeSi intermetallic compound powder and Ni3Si intermetallic compound powder prepared in step 2 and step 4 with 40 parts of TiB2 powder and TiC powder, add 8 parts of Al2O3 powder and 2 parts of Y2O3 powder as sintering aids to the mixed powder to obtain mixed powder C, put the obtained mixed powder C consisting of FeSi intermetallic compound powder and Ni3Si intermetallic compound powder, TiB2 powder and TiC powder, and Al2O3 powder and Y2O3 powder as sintering aids into a ball mill, add 350 ml of anhydrous ethanol and 55 ml of TiB2 powder and TiC powder into the ball mill. A slurry is prepared by mechanical ball milling with an agate grinding ball having a diameter of 15 mm for 24 hours, and the slurry is put into a glass beaker and dried in an oven at 100°C for 24 hours to prepare a FeSi-Ni3Si / TiB2-TiC composite powder; the FeSi intermetallic compound powder and the Ni3Si intermetallic compound powder are 60 parts in the FeSi-Ni3Si / TiB2-TiC composite powder; the FeSi intermetallic compound powder and the Ni3Si intermetallic compound powder are 30 parts in the FeSi-Ni3Si / TiB2-TiC composite powder; the TiB2 ceramic powder is 20 parts and the TiC ceramic powder is 20 parts;

[0116] Step 6: The FeSi-Ni3Si / TiB2-TiC composite powder obtained in step 5 is mixed with 10 parts of phenolic resin binder and then put into a ball mill and add 300 ml of anhydrous ethanol and 30 agate grinding balls with a diameter of 15 mm for mechanical ball milling for 24 hours to prepare a slurry, and the slurry is prepared by wet ball milling. The slurry is put into a glass beaker and dried in an oven at 100°C for 24 hours to prepare a mixed powder D containing a phenolic resin binder. The mixed powder D is put into a steel mold capable of making strip specimens, and is pressed into a strip specimen preform by a pressure forming machine at a pressure of 180 MPa for a holding time of 3 minutes. The size of the strip specimen preform is 50 mm×5 mm×6 mm. The strip sample preform is placed in a drying oven and dried at 150° C. for 24 hours to completely solidify the phenolic resin, thereby obtaining a FeSi-Ni3Si / TiB2-TiC composite powder strip sample preform containing a phenolic resin binder having a certain strength; the strip sample preform is placed in a latex glove, wrapped and sealed with the latex glove, and placed in a cold isostatic press, wherein the medium in the cold isostatic press is hydraulic oil, and the holding time in the cold isostatic press is 5 minutes at a pressure of 180 MPa. After the holding time, the sample is taken out to obtain a dense FeSi-Ni3Si / TiB2-TiC composite powder strip sample preform, wherein the size of the strip sample preform is 50 mm×5 mm×6 mm;

[0117] Step 7: Place the FeSi-Ni3Si / TiB2-TiC composite powder strip sample preformed body prepared by pressure forming in step 6 into a graphite crucible, and place the graphite crucible into a vacuum high-temperature sintering furnace for molten metal liquid phase sintering process; the molten metal liquid phase sintering process is as follows: the sintering temperature is 1750°C, the holding time is 2h, and the molten metal liquid phase sintering process is carried out under vacuum conditions, and the vacuum degree is 10 -2 Pa. The heating rate during the sintering process is 35℃ / min. After the sintering process is completed, the furnace is cooled. FeSi-Ni3Si / TiB2-TiC composite block is prepared by molten metal liquid phase sintering process. The melting point of the FeSi intermetallic compound is 1410°C, and the melting point of the Ni3Si intermetallic compound is 1255°C. When sintered at 1750°C, the FeSi intermetallic compound and the Ni3Si intermetallic compound will melt to form a liquid phase. The FeSi intermetallic compound liquid phase and the Ni3Si intermetallic compound liquid phase will infiltrate into the middle of the TiB2 particles and the TiC particles through the pores in the TiB2 matrix and the TiC matrix, so that the molten FeSi intermetallic compound liquid phase and the molten Ni3Si intermetallic compound liquid phase fill the pores in the TiB2 ceramic and the TiC ceramic matrix. Since the FeSi alloy liquid phase particles and the Ni3Si alloy liquid phase particles have good wettability with the TiB2 particles and the TiC particles, the FeSi intermetallic compound and the Ni3Si intermetallic compound can be well bonded with the TiB2 particles and the TiC particles to form a dense FeSi-Ni3Si / TiB2-TiC composite material sintered block. The higher the content of FeSi alloy and Ni3Si alloy, the denser the FeSi-Ni3Si / TiB2-TiC composite material is. During the sintering process, Al2O3 powder and Y2O3 powder sintering aid react at high temperature to form liquid Y3Al5O 12 , namely YAG phase, forms a liquid phase to promote the densification of the ceramic composite matrix and improve the mechanical properties of the ceramic composite. The phenolic resin binder decomposes into gas at high temperature and evaporates, leaving only a small amount of residual carbon, which is mixed in the sintered sample. The FeSi-Ni3Si / TiB2-TiC composite block has high density and high mechanical properties. The total number of FeSi intermetallic compounds and Ni3Si intermetallic compounds in the FeSi-Ni3Si / TiB2-TiC composite is 60 parts.

[0118] Example 7

[0119] The molten metal liquid phase sintering process of the FeSi-Ni3Si / TiB2-TiC composite material comprises the following steps by weight:

[0120] Step 1: Prepare Fe-Si intermetallic compound powder by mechanical alloying process. The specific steps are:

[0121] Fe-Si intermetallic compound powder is prepared by ball milling for 80 hours using a mechanical alloying process, wherein the ball milling jar is a polytetrafluoroethylene ball milling jar, the grinding balls are agate grinding balls, the mass ratio of the agate grinding balls to the mixed powder is 10:1, wherein the molar ratio of Fe powder to Si powder is 50:50, Fe powder and Si powder are loaded into the ball milling jar of a QM-1SP2 planetary ball mill, and after fixing four ball milling jars, the planetary ball mill is started for mechanical ball milling, the mechanical ball milling time is 80 hours, the speed of the ball mill is 400r / min, dry ball milling is adopted, and intermittent ball milling is adopted, and argon gas is filled in the ball milling jar as a protective gas; Fe-Si intermetallic compound powder is prepared by ball milling for 80 hours using a mechanical alloying process; the purity of the Fe powder is 99%, and the particle size is 75-100μm; the purity of the Si powder is 99%, and the particle size is 75-100μm;

[0122] Step 2: The Fe-Si intermetallic compound powder prepared in step 1 is subjected to a heat treatment process to prepare FeSi intermetallic compound powder. The specific steps are:

[0123] The Fe-Si intermetallic compound powder and 10 parts of phenolic resin binder are placed in a ball mill, and 300 ml of anhydrous ethanol and 30 agate grinding balls with a diameter of 15 mm are added and mechanically ball milled for 24 hours to prepare a slurry, which is then mixed by wet ball milling to prepare a slurry. The slurry is placed in a glass beaker and dried in an oven at 100°C for 24 hours to prepare a mixed powder A, and the mixed powder A is placed in a steel mold that can be made into a strip sample, and is pressed into a strip sample with a pressure molding machine at a pressure of 200 MPa for a holding time of 3 minutes. The size of the strip sample is 50 mm×5 mm×6 mm. The strip sample is placed in a graphite crucible, and the graphite crucible is placed in a vacuum sintering furnace, wherein the heat treatment temperature is 1200°C, the holding time is 1 hour, and the vacuum degree is 10 -2 Pa, to obtain a porous and loose FeSi intermetallic compound powder strip sample, after the heat treatment, the FeSi intermetallic compound strip sample is taken out, crushed and ground into FeSi intermetallic compound powder, to obtain FeSi intermetallic compound powder; a small amount of phenolic resin is completely decomposed and volatilized during the high temperature heat treatment, and no phenolic resin remains in the obtained powder;

[0124] Step 3: Prepare Ni-Si intermetallic compound powder by mechanical alloying process. The specific steps are:

[0125] The Ni-Si intermetallic compound powder is prepared by ball milling for 80 hours using a mechanical alloying process, wherein the ball milling jar is a polytetrafluoroethylene ball milling jar, the grinding balls are agate grinding balls, the mass ratio of the agate grinding balls to the mixed powder is 10:1, wherein the molar ratio of Ni powder to Si powder is 75:25, the Ni powder and Si powder are loaded into the ball milling jar of the QM-1SP2 planetary ball mill, and the planetary ball mill is started for mechanical ball milling after the four ball milling jars are fixed. The mechanical ball milling time is 80 hours, the speed of the ball mill is 400r / min, dry ball milling is adopted, and intermittent ball milling is adopted, argon gas is filled in the ball milling jar as a protective gas, and the Ni-Si intermetallic compound powder is prepared by ball milling for 80 hours using a mechanical alloying process; the purity of the Ni powder is 99%, and the particle size is 75-100μm; the purity of the Si powder is 99%, and the particle size is 75-100μm;

[0126] Step 4: The Ni-Si intermetallic compound powder prepared in step 3 is subjected to a heat treatment process to prepare Ni3Si intermetallic compound powder. The specific steps are:

[0127] The Ni-Si intermetallic compound powder and 10 parts of phenolic resin binder are placed in a ball mill, and 300 ml of anhydrous ethanol and 30 agate grinding balls with a diameter of 15 mm are added and mechanically ball milled for 24 hours to prepare a slurry, which is then mixed by wet ball milling to prepare a slurry, and the slurry is placed in a glass beaker and dried in an oven at 100°C for 24 hours to prepare a mixed powder B, and the mixed powder B is placed in a steel mold that can be made into a strip sample, and is pressed into a strip sample by a pressure molding machine at a pressure of 200 MPa for a holding time of 3 minutes, the size of the strip sample is 50 mm×5 mm×6 mm, and the strip sample is placed in a graphite crucible, and the graphite crucible is placed in a vacuum sintering furnace, wherein the heat treatment temperature is 1200°C, the holding time is 1 hour, and the vacuum degree is 10 -2 Pa to obtain a porous Ni3Si intermetallic compound powder strip sample, after the heat treatment, take out the Ni3Si intermetallic compound strip sample, crush and grind it into Ni3Si intermetallic compound powder, and obtain Ni3Si intermetallic compound powder; a small amount of phenolic resin is completely decomposed and volatilized during the high temperature heat treatment, and no phenolic resin remains in the obtained powder;

[0128] Step 5: 70 parts of the FeSi intermetallic compound powder and the Ni3Si intermetallic compound powder prepared in step 2 and step 4 are mixed with 30 parts of the TiB2 powder and the TiC powder, and 9 parts of Al2O3 powder and 1 part of Y2O3 powder as sintering aids are added to the mixed powder to obtain a mixed powder C. The mixed powder C consisting of the obtained FeSi intermetallic compound powder and the Ni3Si intermetallic compound powder, the TiB2 powder and the TiC powder, and the Al2O3 powder and the Y2O3 powder as sintering aids is placed in a ball mill, and 400 ml of anhydrous ethanol and 60 16-diameter balls are added to the ball mill. The mixture was mechanically ball-milled with agate grinding balls of mm for 24 hours to prepare a slurry, and the slurry was put into a glass beaker and the glass beaker was placed in an oven and dried at 100°C for 24 hours to prepare a FeSi-Ni3Si / TiB2-TiC composite powder; the total number of FeSi intermetallic compound powder and Ni3Si intermetallic compound powder in the FeSi-Ni3Si / TiB2-TiC composite powder was 70 parts; the FeSi intermetallic compound powder and the Ni3Si intermetallic compound powder in the FeSi-Ni3Si / TiB2-TiC composite powder were 35 parts, and the TiB2 powder and the TiC powder were 15 parts;

[0129] Step 6: The FeSi-Ni3Si / TiB2-TiC composite powder obtained in step 5 is mixed with 10 parts of phenolic resin binder, and then put into a ball mill, and 300 ml of anhydrous ethanol and 30 agate grinding balls with a diameter of 15 mm are added, and mechanical ball milling is performed for 24 hours to prepare a slurry, and the slurry is prepared by wet ball milling. The slurry is put into a glass beaker and dried in an oven at 100°C for 24 hours to prepare a mixed powder D containing a phenolic resin binder. The mixed powder D is put into a steel mold capable of making strip specimens, and is pressed into a strip specimen preform by a pressure forming machine at a pressure of 200 MPa for a holding time of 3 minutes. The size of the strip specimen preform is 50 mm×5 mm×6 mm; The preformed sample body is placed in a drying oven and dried at 150° C. for 24 hours to completely solidify the phenolic resin, thereby obtaining a FeSi-Ni3Si / TiB2-TiC composite powder strip sample preformed body containing a phenolic resin binder having a certain strength, and the strip sample preformed body is placed in a latex glove, wrapped with a latex glove, sealed, and placed in a cold isostatic press, wherein the medium in the cold isostatic press is hydraulic oil, and the holding time in the cold isostatic press is 5 minutes at a pressure of 200 MPa. After the holding time, the sample is taken out to form a dense FeSi-Ni3Si / TiB2-TiC composite powder strip sample preformed body, wherein the size of the strip sample preformed body is 50 mm×5 mm×6 mm;

[0130] Step 7: Place the FeSi-Ni3Si / TiB2-TiC composite powder strip sample preformed body prepared by pressure forming in step 6 into a graphite crucible, and place the graphite crucible into a vacuum high-temperature sintering furnace for a molten metal liquid phase sintering process; the molten metal liquid phase sintering process is as follows: the sintering temperature is 1800°C, the holding time is 2h, and the molten metal liquid phase sintering process is carried out under vacuum conditions, and the vacuum degree is 10 -2 Pa; the heating rate during the sintering process is 35℃ / min. After the sintering process is completed, the furnace is cooled. The FeSi-Ni3Si / TiB2-TiC composite material block is prepared by the molten metal liquid phase sintering process. The melting point of the FeSi intermetallic compound is 1410°C, and the melting point of the Ni3Si intermetallic compound is 1255°C. When sintered at 1800°C, the FeSi intermetallic compound and the Ni3Si intermetallic compound will melt to form a liquid phase. The FeSi intermetallic compound liquid phase and the Ni3Si intermetallic compound liquid phase will infiltrate into the middle of the TiB2 particles and the TiC particles through the pores in the TiB2 matrix and the TiC matrix, so that the molten FeSi intermetallic compound liquid phase and the molten Ni3Si intermetallic compound liquid phase fill the pores in the TiB2 ceramic and the TiC ceramic matrix. Since the FeSi alloy liquid phase particles and the Ni3Si alloy liquid phase particles have good wettability with the TiB2 particles and the TiC particles, the FeSi intermetallic compound and the Ni3Si intermetallic compound can be well bonded with the TiB2 particles and the TiC particles to form a dense FeSi-Ni3Si / TiB2-TiC composite material sintered block. Moreover, the higher the content of FeSi alloy and Ni3Si alloy, the denser the FeSi-Ni3Si / TiB2-TiC composite material is. During the sintering process, Al2O3 powder and Y2O3 powder sintering aid react at high temperature to form liquid Y3Al5O 12 , namely YAG phase, forms a liquid phase to promote the densification of the ceramic composite matrix and improve the mechanical properties of the ceramic composite. The phenolic resin binder decomposes into gas and evaporates at high temperature, leaving only a small amount of residual carbon, which is mixed in the sintered sample. The FeSi-Ni3Si / TiB2-TiC composite block has high density and high mechanical properties. The total number of FeSi intermetallic compounds and Ni3Si intermetallic compounds in the FeSi-Ni3Si / TiB2-TiC composite is 70 parts.

[0131] Example 8

[0132] The FeSi-Ni3Si / TiB2-TiC composite material includes the following components in parts by mass:

[0133] In the FeSi-Ni3Si / TiB2-TiC composite material, FeSi intermetallic compound and Ni3Si intermetallic compound are used as the strengthening and toughening phase, and the strengthening and toughening phase accounts for 10 parts; TiB2 and TiC are used as the matrix, and the matrix accounts for 90 parts; Al2O3 powder accounts for 3 parts; Y2O3 powder accounts for 7 parts; Al2O3 powder and Y2O3 powder are used as sintering aids; phenolic resin binder accounts for 9 parts;

[0134] The mass ratio of the FeSi intermetallic compound to the Ni3Si intermetallic compound is 1:1. The mass ratio of the TiB2 ceramic to the TiC ceramic is 1:1.

[0135] The FeSi intermetallic compound powder is prepared by mechanical alloying and heat treatment process, and the Fe-Si intermetallic compound powder A is prepared by ball milling for 80 hours using the mechanical alloying process, wherein the molar ratio of Fe:Si is 50:50;

[0136] The Ni3Si intermetallic compound powder is prepared by mechanical alloying and heat treatment process. The Ni-Si intermetallic compound powder B is prepared by ball milling for 80 hours using the mechanical alloying process, wherein the molar ratio of Ni:Si is 75:25; and the prepared Fe-Si intermetallic compound powder and Ni-Si intermetallic compound powder are subjected to heat treatment process respectively, the heat treatment temperature is 800°C, the heat preservation time is 1h, and the vacuum degree is 10 -2 The heat treatment process was carried out under the condition of Pa to prepare FeSi intermetallic compound powder and Ni3Si intermetallic compound powder respectively.

[0137] Example 9

[0138] The FeSi-Ni3Si / TiB2-TiC composite material comprises the following components in parts by mass:

[0139] In the FeSi-Ni3Si / TiB2-TiC composite material, FeSi intermetallic compound and Ni3Si intermetallic compound are used as the strengthening and toughening phase, and the strengthening and toughening phase accounts for 20 parts; TiB2 and TiC are used as the matrix, and the matrix accounts for 80 parts; Al2O3 powder accounts for 4 parts; Y2O3 powder accounts for 6 parts; Al2O3 powder and Y2O3 powder are used as sintering aids; phenolic resin binder accounts for 10 parts;

[0140] The mass ratio of the FeSi intermetallic compound to the Ni3Si intermetallic compound is 1:1. The mass ratio of the TiB2 ceramic to the TiC ceramic is 1:1.

[0141] The FeSi intermetallic compound powder is prepared by mechanical alloying and heat treatment process, and the Fe-Si intermetallic compound powder A is prepared by ball milling for 80 hours using the mechanical alloying process, wherein the molar ratio of Fe:Si is 50:50;

[0142] The Ni3Si intermetallic compound powder is prepared by mechanical alloying and heat treatment process. The Ni-Si intermetallic compound powder B is prepared by ball milling for 80 hours using the mechanical alloying process, wherein the molar ratio of Ni:Si is 75:25; and the prepared Fe-Si intermetallic compound powder and Ni-Si intermetallic compound powder are subjected to heat treatment process respectively, the heat treatment temperature is 900°C, the heat preservation time is 1h, and the vacuum degree is 10 -2 The heat treatment process was carried out under the condition of Pa to prepare FeSi intermetallic compound powder and Ni3Si intermetallic compound powder respectively.

[0143] Example 10

[0144] The FeSi-Ni3Si / TiB2-TiC composite material comprises the following components in parts by mass:

[0145] In the FeSi-Ni3Si / TiB2-TiC composite material, FeSi intermetallic compound and Ni3Si intermetallic compound are used as the strengthening and toughening phase, and the strengthening and toughening phase accounts for 30 parts; TiB2 and TiC are used as the matrix, and the matrix accounts for 70 parts; Al2O3 powder accounts for 5 parts; Y2O3 powder accounts for 5 parts; Al2O3 powder and Y2O3 powder are used as sintering aids; phenolic resin binder accounts for 9 parts;

[0146] The mass ratio of the FeSi intermetallic compound to the Ni3Si intermetallic compound is 1:1. The mass ratio of the TiB2 ceramic to the TiC ceramic is 1:1.

[0147] The FeSi intermetallic compound powder is prepared by mechanical alloying and heat treatment process, and the Fe-Si intermetallic compound powder A is prepared by ball milling for 80 hours using the mechanical alloying process, wherein the molar ratio of Fe:Si is 50:50;

[0148] The Ni3Si intermetallic compound powder is prepared by mechanical alloying and heat treatment process. The Ni-Si intermetallic compound powder B is prepared by ball milling for 80 hours using the mechanical alloying process, wherein the molar ratio of Ni:Si is 75:25; and the prepared Fe-Si intermetallic compound powder and Ni-Si intermetallic compound powder are subjected to heat treatment process respectively, the heat treatment temperature is 1000°C, the heat preservation time is 1h, and the vacuum degree is 10 -2The heat treatment process was carried out under the condition of Pa to prepare FeSi intermetallic compound powder and Ni3Si intermetallic compound powder respectively.

[0149] Embodiment 11

[0150] The FeSi-Ni3Si / TiB2-TiC composite material comprises the following components in parts by mass:

[0151] In the FeSi-Ni3Si / TiB2-TiC composite material, FeSi intermetallic compound and Ni3Si intermetallic compound are used as the strengthening and toughening phase, and the strengthening and toughening phase accounts for 40 parts; TiB2 and TiC are used as the matrix, and the matrix accounts for 60 parts; Al2O3 powder accounts for 6 parts; Y2O3 powder accounts for 4 parts; Al2O3 powder and Y2O3 powder are used as sintering aids; phenolic resin binder accounts for 10 parts;

[0152] The mass ratio of the FeSi intermetallic compound to the Ni3Si intermetallic compound is 1:1; the mass ratio of the TiB2 ceramic to the TiC ceramic is 1:1.

[0153] The FeSi intermetallic compound powder is prepared by mechanical alloying and heat treatment process, and the Fe-Si intermetallic compound powder A is prepared by ball milling for 80 hours using the mechanical alloying process, wherein the molar ratio of Fe:Si is 50:50;

[0154] The Ni3Si intermetallic compound powder is prepared by mechanical alloying and heat treatment process. The Ni-Si intermetallic compound powder B is prepared by ball milling for 80 hours using the mechanical alloying process, wherein the molar ratio of Ni:Si is 75:25; and the prepared Fe-Si intermetallic compound powder and Ni-Si intermetallic compound powder are subjected to heat treatment process respectively, the heat treatment temperature is 1050°C, the heat preservation time is 1h, and the vacuum degree is 10 -2 The heat treatment process was carried out under the condition of Pa to prepare FeSi intermetallic compound powder and Ni3Si intermetallic compound powder respectively.

[0155] Example 12

[0156] The FeSi-Ni3Si / TiB2-TiC composite material comprises the following components in parts by mass:

[0157] In the FeSi-Ni3Si / TiB2-TiC composite material, FeSi intermetallic compound and Ni3Si intermetallic compound are used as the strengthening and toughening phase, and the strengthening and toughening phase accounts for 50 parts; TiB2 and TiC are used as the matrix, and the matrix accounts for 50 parts; Al2O3 powder accounts for 7 parts; Y2O3 powder accounts for 3 parts; Al2O3 powder and Y2O3 powder are used as sintering aids; phenolic resin binder accounts for 10 parts;

[0158] The mass ratio of the FeSi intermetallic compound to the Ni3Si intermetallic compound is 1:1. The mass ratio of the TiB2 ceramic to the TiC ceramic is 1:1.

[0159] The FeSi intermetallic compound powder is prepared by mechanical alloying and heat treatment process, and the Fe-Si intermetallic compound powder A is prepared by ball milling for 80 hours using the mechanical alloying process, wherein the molar ratio of Fe:Si is 50:50;

[0160] The Ni3Si intermetallic compound powder is prepared by mechanical alloying and heat treatment process. The Ni-Si intermetallic compound powder B is prepared by ball milling for 80 hours using the mechanical alloying process, wherein the molar ratio of Ni:Si is 75:25; and the prepared Fe-Si intermetallic compound powder and Ni-Si intermetallic compound powder are subjected to heat treatment process respectively, the heat treatment temperature is 1100°C, the heat preservation time is 1h, and the vacuum degree is 10 -2 The heat treatment process was carried out under the condition of Pa to prepare FeSi intermetallic compound powder and Ni3Si intermetallic compound powder respectively.

[0161] Example 13

[0162] The FeSi-Ni3Si / TiB2-TiC composite material comprises the following components in parts by mass:

[0163] In the FeSi-Ni3Si / TiB2-TiC composite material, FeSi intermetallic compound and Ni3Si intermetallic compound are used as the strengthening and toughening phase, and the strengthening and toughening phase accounts for 60 parts; TiB2 and TiC are used as the matrix, and the matrix accounts for 40 parts; Al2O3 powder accounts for 8 parts; Y2O3 powder accounts for 2 parts; Al2O3 powder and Y2O3 powder are used as sintering aids; phenolic resin binder accounts for 10 parts;

[0164] The mass ratio of the FeSi intermetallic compound to the Ni3Si intermetallic compound is 1:1. The mass ratio of the TiB2 ceramic to the TiC ceramic is 1:1.

[0165] The FeSi intermetallic compound powder is prepared by mechanical alloying and heat treatment process, and the Fe-Si intermetallic compound powder A is prepared by ball milling for 80 hours using the mechanical alloying process, wherein the molar ratio of Fe:Si is 50:50;

[0166] The Ni3Si intermetallic compound powder is prepared by mechanical alloying and heat treatment process. The Ni-Si intermetallic compound powder B is prepared by ball milling for 80 hours using the mechanical alloying process, wherein the molar ratio of Ni:Si is 75:25; and the prepared Fe-Si intermetallic compound powder and Ni-Si intermetallic compound powder are subjected to heat treatment process respectively, the heat treatment temperature is 1150°C, the heat preservation time is 1h, and the vacuum degree is 10 -2 The heat treatment process was carried out under the condition of Pa to prepare FeSi intermetallic compound powder and Ni3Si intermetallic compound powder respectively.

[0167] Embodiment 14

[0168] The FeSi-Ni3Si / TiB2-TiC composite material comprises the following components in parts by mass:

[0169] In the FeSi-Ni3Si / TiB2-TiC composite material, FeSi intermetallic compound and Ni3Si intermetallic compound are used as the strengthening and toughening phase, and the strengthening and toughening phase accounts for 70 parts; TiB2 and TiC are used as the matrix, and the matrix accounts for 30 parts; Al2O3 powder accounts for 9 parts; Y2O3 powder accounts for 1 part; wherein Al2O3 powder and Y2O3 powder are used as sintering aids; phenolic resin binder accounts for 10 parts;

[0170] The mass ratio of the FeSi intermetallic compound to the Ni3Si intermetallic compound is 1:1. The mass ratio of the TiB2 ceramic to the TiC ceramic is 1:1.

[0171] The FeSi intermetallic compound powder is prepared by mechanical alloying and heat treatment process, and the Fe-Si intermetallic compound powder A is prepared by ball milling for 80 hours using the mechanical alloying process, wherein the molar ratio of Fe:Si is 50:50;

[0172] The Ni3Si intermetallic compound powder is prepared by mechanical alloying and heat treatment process. The Ni-Si intermetallic compound powder B is prepared by ball milling for 80 hours using the mechanical alloying process, wherein the molar ratio of Ni:Si is 75:25; and the prepared Fe-Si intermetallic compound powder and Ni-Si intermetallic compound powder are subjected to heat treatment process respectively, the heat treatment temperature is 1200°C, the heat preservation time is 1h, and the vacuum degree is 10 -2 The heat treatment process was carried out under the condition of Pa to prepare FeSi intermetallic compound powder and Ni3Si intermetallic compound powder respectively.

[0173] It can be seen from Examples 1-7 that the molten metal liquid phase sintering process used in Examples 1-7 has a simple preparation process and low cost, and does not require the use of complex and expensive hot pressing sintering equipment, spark plasma sintering equipment, and hot isostatic pressing sintering equipment. The molten metal liquid phase sintering process used only requires a vacuum high-temperature sintering furnace, and any vacuum high-temperature sintering furnace with a sintering temperature below 2000°C can be used. Since the vacuum high-temperature sintering furnace does not have a complex pressurization system, the equipment cost is low. The molten metal liquid phase sintering process has a low preparation cost and a simple preparation process, and can also prepare dense composite material blocks. Therefore, the main advantages of the present invention over existing technologies are:

[0174] 1) The present invention adopts a mechanical alloying process combined with a heat treatment process to prepare FeSi intermetallic compound powder and Ni3Si intermetallic compound powder, and prepares Fe-Si intermetallic compound powder and Ni-Si intermetallic compound powder by ball milling for 80 hours through the mechanical alloying process, and prepares FeSi intermetallic compound powder and Ni3Si intermetallic compound powder through a heat treatment process with a heat treatment temperature of 800°C to 1200°C and a holding time of 1 hour, and mixes the FeSi intermetallic compound powder and Ni3Si intermetallic compound powder with TiB2 powder and TiC powder, and adds 10 parts by mass of Al2O3 powder and Y2O3 powder sintering aids to prepare FeSi-Ni3Si / TiB2-TiC composite powder through wet ball milling and drying, and prepares FeSi-Ni3Si / TiB2-TiC composite powder through pressure molding to make strip samples, and prepares FeSi-Ni3Si / TiB2-TiC composite material blocks through a molten metal liquid phase sintering process. The molten metal liquid phase sintering process has low preparation cost, simple preparation process, high preparation efficiency, and can also prepare FeSi-Ni3Si / TiB2-TiC composite block with uniform and dense organizational structure, and the FeSi-Ni3Si / TiB2-TiC composite block prepared by the molten metal liquid phase sintering method has high mechanical properties and excellent wear resistance. The molten metal liquid phase sintering method can be used to produce FeSi-Ni3Si / TiB2-TiC composite products with complex shapes.

[0175] 2) In the preparation process of FeSi-Ni3Si / TiB2-TiC composite material block, the role of adding 10 parts by mass of Al2O3 powder and Y2O3 powder sintering aids is that during the sintering process, the Al2O3 powder and Y2O3 powder sintering aids react at high temperature to form liquid Y3Al5O 12, namely YAG phase, forms a liquid phase to promote the densification of the ceramic composite matrix, plays a role in filling pores, and improves the mechanical properties of the ceramic composite. The purpose of adding 10 parts by mass of phenolic resin binder to the Fe-Si intermetallic compound powder is to improve the strength and hardness of the strip sample blank after pressure molding, prevent fracture and damage during sample taking and placing in a graphite crucible, and ensure the integrity of the sample. The phenolic resin binder is completely decomposed into gas and volatilized at high temperature, and there is no residual phenolic resin in the obtained powder. The purpose of adding 10 parts by mass of phenolic resin binder to the Ni-Si intermetallic compound powder is to improve the strength and hardness of the strip sample blank after pressure molding, prevent fracture and damage during sample taking and placing in a graphite crucible, and ensure the integrity of the sample. The phenolic resin binder is completely decomposed into gas and volatilized at high temperature, and there is no residual phenolic resin in the obtained powder. The purpose of adding 10 parts by mass of phenolic resin binder to the FeSi-Ni3Si / TiB2-TiC composite powder is to improve the strength and hardness of the strip sample blank after pressure forming, prevent breakage and damage when taking the sample and placing it in the graphite crucible, and ensure the integrity of the sample. The phenolic resin binder decomposes into gas at high temperature and evaporates, leaving only a small amount of residual carbon. A small amount of residual carbon is mixed in the sintered sample and will not affect the final product.

[0176] 3) The FeSi-Ni3Si / TiB2-TiC composite material prepared by the molten metal liquid phase sintering process has a uniform and dense microstructure and high mechanical properties, and also has the high strength and high toughness, high hardness, high elastic modulus and other properties of FeSi intermetallic compounds and Ni3Si intermetallic compounds. The FeSi-Ni3Si / TiB2-TiC composite material prepared by the molten metal liquid phase sintering process has a high density and a uniform and dense microstructure. The FeSi-Ni3Si / TiB2-TiC composite material prepared by the molten metal liquid phase sintering process has high mechanical properties and high hardness, as well as good wear resistance and high temperature oxidation resistance. The present invention develops a new preparation process for the low-cost manufacture of FeSi-Ni3Si / TiB2-TiC composite materials, and the present invention lays a foundation for popularizing and promoting the wide application of FeSi-Ni3Si / TiB2-TiC composite materials in the engineering field.

[0177] Figure 1 The invention discloses an X-ray diffraction spectrum of a FeSi-Ni3Si / TiB2-TiC composite material block prepared by a molten metal liquid phase sintering process according to the method provided by the invention. Figure 1 The XRD pattern of FeSi-Ni3Si / TiB2-TiC composite material block prepared by molten metal liquid phase sintering process. Figure 1 It can be seen that in the XRD spectrum, there are diffraction peaks of FeSi intermetallic compound and Ni3Si intermetallic compound phase, as well as diffraction peaks of TiB2 ceramic phase and TiC ceramic phase. In addition, there is a small amount of Y3Al5O 12 The diffraction peak of the phase is the diffraction peak of the YAG phase. During the sintering process, the Al2O3 powder and the Y2O3 powder sintering aid react at high temperature to form liquid Y3Al5O 12, namely YAG phase, forming a liquid phase to promote the densification of the ceramic composite matrix and improve the mechanical properties of the ceramic composite. In the XRD spectrum, there are diffraction peaks of FeSi intermetallic compounds and Ni3Si intermetallic compound phases, as well as diffraction peaks of TiB2 ceramic phases and TiC ceramic phases, which shows that during the preparation process of molten metal liquid phase sintering, FeSi intermetallic compounds and Ni3Si intermetallic compounds do not react with TiB2 ceramics and TiC ceramics to generate other impurity phases, and FeSi intermetallic compounds and Ni3Si intermetallic compounds have good compatibility with TiB2 ceramics and TiC ceramics. Through the molten metal liquid phase sintering process, FeSi intermetallic compounds and Ni3Si intermetallic compounds can be sintered together with TiB2 ceramics and TiC ceramics to form a dense FeSi-Ni3Si / TiB2-TiC composite material, in which FeSi intermetallic compounds and Ni3Si intermetallic compounds are reinforcing and toughening phases, and TiB2 ceramics and TiC ceramics are the matrix. FeSi intermetallic compounds and Ni3Si intermetallic compounds play a role in strengthening and toughening TiB2 ceramics and TiC ceramics. FeSi intermetallic compounds and Ni3Si intermetallic compounds can significantly improve the mechanical properties of TiB2 ceramics and TiC ceramics. FeSi-Ni3Si / TiB2-TiC composite materials have the excellent properties of FeSi intermetallic compounds and Ni3Si intermetallic compounds, and also have the excellent properties of TiB2 ceramics and TiC ceramics. The present invention develops a new preparation process for low-cost manufacturing of FeSi-Ni3Si / TiB2-TiC composite materials. The FeSi-Ni3Si / TiB2-TiC composite materials prepared by the molten metal liquid phase sintering process have high preparation efficiency and low preparation cost. The FeSi-Ni3Si / TiB2-TiC composite materials prepared by the molten metal liquid phase sintering process have high density and uniform and dense microstructure. The FeSi-Ni3Si / TiB2-TiC composite materials prepared by the molten metal liquid phase sintering process have high mechanical properties and high hardness, as well as good wear resistance and good high temperature oxidation resistance. The present invention develops a new preparation process for low-cost manufacturing of FeSi-Ni3Si / TiB2-TiC composite materials, and the present invention lays a foundation for popularizing and promoting the wide application of FeSi-Ni3Si / TiB2-TiC composite materials in the engineering field.

Claims

1. FeSi-Ni3Si / TiB2-TiC composite material, characterized in that: According to the mass percentage, it includes the following components: FeSi intermetallic compound and Ni3Si intermetallic compound are used as strengthening and toughening phases, TiB2 and TiC are used as matrix; Al2O3 and Y2O3 are used as sintering aids; a small amount of phenolic resin is used as binder; The mass fraction of FeSi intermetallic compound powder is 5 to 35 parts; the mass fraction of Ni3Si intermetallic compound powder is 5 to 35 parts; the mass fraction of TiB2 powder is 15 to 45 parts; the mass fraction of TiC powder is 15 to 45 parts; the mass fraction of Al2O3 powder is 3 to 9 parts; the mass fraction of Y2O3 powder is 1 to 7 parts; the mass fraction of phenolic resin binder is 9 to 10 parts; The mass ratio of the FeSi intermetallic compound powder to the Ni3Si intermetallic compound powder is 1:

1.

2. The FeSi-Ni3Si / TiB2-TiC composite material according to claim 1, characterized in that: The molar ratio of Fe powder to Si powder in the FeSi intermetallic compound powder is 50:50; The molar ratio of Ni powder to Si powder in the Ni3Si intermetallic compound powder is 75:25; Both FeSi intermetallic compound powder and Ni3Si intermetallic compound powder are prepared by mechanical alloying process and heat treatment process.

3. The molten metal liquid phase sintering process of the FeSi-Ni3Si / TiB2-TiC composite material according to claim 1, characterized in that, by weight, The following steps are involved: Step 1: prepare Fe-Si intermetallic compound powder by mechanical alloying process, the specific steps are: Fe-Si intermetallic compound powder is prepared by ball milling for 80 hours using a mechanical alloying process, wherein the ball milling jar is a polytetrafluoroethylene ball milling jar, the grinding balls are agate grinding balls, the mass ratio of the agate grinding balls to the mixed powder is 10:1, wherein the molar ratio of Fe powder to Si powder is 50:50, Fe powder and Si powder are loaded into the ball milling jar of a QM-1SP2 planetary ball mill, and after fixing four ball milling jars, the planetary ball mill is started for mechanical ball milling, the mechanical ball milling time is 80 hours, the speed of the ball mill is 400r / min, dry ball milling is adopted, and intermittent ball milling is adopted, argon gas is filled into the ball milling jar as a protective gas, and Fe-Si intermetallic compound powder is prepared by ball milling for 80 hours using a mechanical alloying process; the purity of the Fe powder is 99%, and the particle size is 75-100μm; the purity of the Si powder is 99%, and the particle size is 75-100μm; Step 2: The Fe-Si intermetallic compound powder prepared in step 1 is subjected to a heat treatment process to prepare FeSi intermetallic compound powder. The specific steps are: The Fe-Si intermetallic compound powder and 10 parts of phenolic resin binder are placed in a ball mill, and 300 ml of anhydrous ethanol and 30 agate grinding balls with a diameter of 15 mm are added. The mixture is mechanically ball-milled for 24 hours to prepare a slurry, which is then mixed by wet ball milling to prepare a slurry. The slurry is placed in a glass beaker, and the glass beaker is placed in an oven and dried at 100°C for 24 hours to prepare a mixed powder A. The mixed powder A is placed in a steel mold for preparing a strip sample, and is pressed into a strip sample by a pressure molding machine at a pressure of 100MPa to 200MPa for a holding time of 3 minutes. The size of the strip sample is 50mm×5mm×6mm, and the strip sample is placed in a graphite crucible, and the graphite crucible is placed in a vacuum sintering furnace, wherein the heat treatment temperature is 800°C to 1200°C, the holding time is 1h, and the vacuum degree is 10 -2 Pa, a FeSi intermetallic compound powder strip sample with a porous structure is obtained through a heat treatment process, after the heat treatment process, the FeSi intermetallic compound strip sample is taken out, crushed and ground into FeSi intermetallic compound powder, and FeSi intermetallic compound powder is prepared through a heat treatment process; a small amount of phenolic resin is completely decomposed and volatilized during the high-temperature heat treatment process, and no phenolic resin remains in the obtained powder; Step 3: Prepare Ni-Si intermetallic compound powder by mechanical alloying process. The specific steps are: A Ni-Si intermetallic compound powder is prepared by ball milling for 80 hours using a mechanical alloying process, wherein a polytetrafluoroethylene ball mill is used as a ball mill, agate balls are used as grinding balls, the mass ratio of agate balls to mixed powder is 10:1, and the molar ratio of Ni powder to Si powder is 75:25; Ni powder and Si powder are loaded into a ball mill of a QM-1SP2 planetary ball mill, and after four ball mills are fixed, the planetary ball mill is started for mechanical ball milling, the mechanical ball milling time is 80 hours, the speed of the ball mill is 400r / min, dry ball milling is adopted, and intermittent ball milling is adopted, argon gas is filled into the ball mill as a protective gas, and Ni-Si intermetallic compound powder is prepared; the purity of the Ni powder is 99%, and the particle size is 75-100μm; the purity of the Si powder is 99%, and the particle size is 75-100μm; Step 4: The Ni-Si intermetallic compound powder prepared in step 3 is subjected to a heat treatment process to prepare Ni3Si intermetallic compound powder. The specific steps are: The Ni-Si intermetallic compound powder and 10 parts of phenolic resin binder are placed in a ball mill, and 300 ml of anhydrous ethanol and 30 agate grinding balls with a diameter of 15 mm are added and mechanically ball milled for 24 hours to prepare a slurry, which is then mixed by wet ball milling to prepare a slurry, and the slurry is placed in a glass beaker, and the glass beaker is placed in an oven and dried at 100°C for 24 hours to prepare a mixed powder B, and the mixed powder B is placed in a steel mold for preparing a strip sample, and is pressed into a strip sample by a pressure molding machine at a pressure of 100MPa to 200MPa for a holding time of 3 minutes, and the size of the strip sample is 50mm×5mm×6mm, and the strip sample is placed in a graphite crucible, and the graphite crucible is placed in a vacuum sintering furnace, wherein the heat treatment temperature is 800°C to 1200°C, the holding time is 1h, and the vacuum degree is 10 -2 Pa, a porous Ni3Si intermetallic compound powder strip sample is obtained through the heat treatment process, and the Ni3Si intermetallic compound strip sample is taken out after the heat treatment process, and then crushed and ground into Ni3Si intermetallic compound powder; Ni3Si intermetallic compound powder is prepared through the heat treatment process; a small amount of phenolic resin is completely decomposed and volatilized during the high-temperature heat treatment process, and no phenolic resin remains in the obtained powder; Step 5: Mix 5 to 35 parts of the FeSi intermetallic compound powder and 5 to 35 parts of the Ni3Si intermetallic compound powder prepared in step 2 and step 4 with 15 to 45 parts of TiB2 powder and 15 to 45 parts of TiC powder, add 3 to 9 parts of Al2O3 powder and 1 to 7 parts of Y2O3 powder as sintering aids to the mixed powder to obtain mixed powder C, put the mixed powder C into a ball mill, add 100 to 400 ml of anhydrous ethanol and 30 to 400 ml of sintered aluminum to the ball mill, and add 100 to 400 ml of anhydrous ethanol and 30 to 40 ml of sintered aluminum to the ball mill. 60 agate grinding balls with a diameter of 10 to 16 mm were mechanically ball-milled for 24 hours to prepare a slurry, and the slurry was put into a glass beaker and the glass beaker was placed in an oven and dried at 100°C for 24 hours to prepare a FeSi-Ni3Si / TiB2-TiC composite powder; the mass ratio of the FeSi intermetallic compound powder to the Ni3Si intermetallic compound powder in the FeSi-Ni3Si / TiB2-TiC composite powder was 1:1; the mass ratio of the TiB2 powder to the TiC powder was 1:1; Step 6: The FeSi-Ni3Si / TiB2-TiC composite powder obtained in step 5 is mixed with 9 to 10 parts of a phenolic resin binder to prepare a mixed powder, which is then loaded into a ball mill and mixed with 300 ml of anhydrous ethanol and 30 agate grinding balls with a diameter of 15 mm for mechanical ball milling for 24 hours to prepare a slurry, which is then mixed by wet ball milling to prepare a slurry and loaded into a glass beaker, and the glass beaker is placed in an oven and dried at 100°C for 24 hours to prepare a mixed powder D containing a phenolic resin binder, and the mixed powder D containing a small amount of phenolic resin binder is loaded into a steel mold for preparing a strip sample, and is pressed into a strip sample preform by a pressure molding machine at a pressure of 100 MPa to 200 MPa for a holding time of 3 minutes, and the size of the strip sample preform is 50 mm×5 mm×6 mm; The sample preform is placed in a drying oven and dried at 150° C. for 24 hours to completely solidify the phenolic resin, thereby obtaining a FeSi-Ni3Si / TiB2-TiC composite powder strip sample preform containing a phenolic resin binder having a certain strength. The FeSi-Ni3Si / TiB2-TiC composite powder strip sample preform is placed in a latex glove, wrapped and sealed with a latex glove, and placed in a cold isostatic press. The medium in the cold isostatic press is hydraulic oil. The holding time in the cold isostatic press is 5 minutes at a pressure of 100 MPa to 200 MPa. After the holding time, the sample is taken out and isostatically pressed by the cold isostatic press to form a dense FeSi-Ni3Si / TiB2-TiC composite powder strip sample preform. The size of the strip sample preform is 50 mm×5 mm×6 mm. Step 7: Place the FeSi-Ni3Si / TiB2-TiC composite powder strip sample preform prepared by pressure forming in step 6 into a graphite crucible, and place the graphite crucible into a vacuum high-temperature sintering furnace for molten metal liquid phase sintering process to prepare FeSi-Ni3Si / TiB2-TiC composite material block; the molten metal liquid phase sintering process is as follows: the sintering temperature is 1500°C to 1800°C, the holding time is 2h, and the molten metal liquid phase sintering process is carried out under vacuum conditions, and the vacuum degree is 10 -2 Pa, the heating rate during the sintering process is 10-35℃ / min, and the furnace is cooled after the sintering process.

4. The molten metal liquid phase sintering process of the FeSi-Ni3Si / TiB2-TiC composite material according to claim 3 is characterized in that: The average particle size of the FeSi intermetallic compound powder and the Ni3Si intermetallic compound powder is 10-15 μm, and the powder particle size is extremely fine; the FeSi intermetallic compound powder and the Ni3Si intermetallic compound powder have an ordered structure.

5. The molten metal liquid phase sintering process of the FeSi-Ni3Si / TiB2-TiC composite material according to claim 3, characterized in that: Step 5: The particle size of the TiB2 powder is 5-8 μm and the particle size of the TiC powder is 5-8 μm; the mass fractions of the FeSi intermetallic compound powder and the Ni3Si intermetallic compound powder in the FeSi-Ni3Si / TiB2-TiC composite powder are 10 to 70 parts; the mass ratio of the FeSi intermetallic compound powder and the Ni3Si intermetallic compound powder is 1:1; the mass ratio of the TiB2 ceramic powder and the TiC ceramic powder is 1:1.